structure

CN123023199APending Publication Date: 2026-10-30ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580022039.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-14
Filing Date
2025-03-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

通常,与低频率的电磁波相比,高频率的电磁波容易衰减,通信区域被限定

Benefits of technology

[0046]根据本发明的一个方式,能够提供具有薄层结构且电磁波控制效率高的结构体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123023199A_ABST
    Figure CN123023199A_ABST
Patent Text Reader

Abstract

Provided is a structure that is a structure having, in order, a first metal pattern layer, a first dielectric layer, a second metal pattern layer, a second dielectric layer, and a third metal pattern layer, wherein the first metal pattern layer and the third metal pattern layer are slit-shaped structures, and the second metal pattern layer contains super-atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to structures. Background Technology

[0002] In recent years, the development of remote operation technology for electronic devices and the widespread adoption of VR have created a demand for higher-speed and higher-capacity communication. To achieve this, higher-frequency electromagnetic waves are required. However, compared to lower-frequency electromagnetic waves, higher-frequency electromagnetic waves are more prone to attenuation, thus limiting the communication area. Therefore, electromagnetic wave control elements capable of collimating or focusing electromagnetic waves to achieve directional control are desired.

[0003] For example, research is underway on controlling the direction of electromagnetic waves by using metamaterials (more specifically, artificial materials that exhibit behaviors relative to electromagnetic waves that are not found in natural matter, through periodic structures with dimensions smaller than the wavelength of the electromagnetic wave).

[0004] For example, Patent Document 1 discloses a lens antenna device, which is equipped with a dielectric lens, a horn antenna, a reflector, and an electromagnetic transceiver. The lens antenna device is characterized in that it makes the electromagnetic waves directional and has low signal loss.

[0005] For example, Patent Document 2 discloses a lens antenna that arranges dielectric lenses with different incident and exit directions of electromagnetic waves into an array, which can scan the incident and exit directions of electromagnetic waves while suppressing gain loss.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-17878

[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-197656 Summary of the Invention

[0010] The problem that the invention aims to solve

[0011] However, electromagnetic wave control elements such as lens antennas that use dielectric lenses as lenses to direct electromagnetic waves, as described in Patent Documents 1 and 2, have the following problem: as the intensity of the incident and emitted electromagnetic waves increases, the dielectric lens also becomes larger and wider. Patent Documents 1 and 2 do not adequately address the aforementioned problems caused by dielectric lenses.

[0012] The purpose of this invention is to solve the above-mentioned problems and provide a structure with a thin-layer structure and high electromagnetic wave control efficiency.

[0013] Methods for solving problems

[0014] This disclosure includes the following items.

[0015] [Item 1]

[0016] A structure comprising, sequentially having a first metal pattern layer, a first dielectric layer, a second metal pattern layer, a second dielectric layer, and a third metal pattern layer, wherein, The first and third metal pattern layers described above have a slit-like structure. The aforementioned second metal patterned layer contains metaatoms.

[0017] [Item 2]

[0018] According to the structure described in item 1, a metal compound layer is further present inside the aforementioned metaatoms.

[0019] [Item 3]

[0020] The structure according to item 1 or 2, wherein the aforementioned metaatoms comprise copper.

[0021] [Item 4]

[0022] According to the structure described in item 2, the aforementioned metaatoms and the aforementioned metal compound layer contain copper.

[0023] [Item 5]

[0024] The structure according to any one of items 1 to 4, wherein a resin layer is further provided on the outer side of the first metal pattern layer and the third metal pattern layer.

[0025] [Item 6]

[0026] The structure according to any one of items 1 to 5, wherein the relative permittivity of the first dielectric layer is set to ε r1 Let the thickness of the first dielectric layer be S1 [μm], and let the relative permittivity of the second dielectric layer be ε. r2 When the thickness of the second dielectric layer is set to S2 [μm], ε r2 / ε r1 When S2 / S1 is above 0.9 and below 1.1, In ε r1 With ε r2 Let the average value be ε r Let the average value of S1 and S2 be S[μm]. When the width of the superatoms is set as w[μm], the thickness of the superatoms is set as t[μm], and the wavelength of the incident electromagnetic wave is set as λ[μm], the following equation (1) is satisfied.

[0027]

[0028] (In equation (1), n ​​is an integer greater than or equal to 0.)

[0029] [Item 7]

[0030] The structure according to any one of items 1 to 6, wherein the second metal pattern layer is a three-dimensional curved surface shape.

[0031] [Item 8]

[0032] The structure according to any one of items 1 to 7, wherein the carbon / metal elemental concentration ratio of the aforementioned metaatoms is 0.05 or more and 6.0 or less.

[0033] [Item 9]

[0034] According to any one of claims 1 to 8, the water absorption rate of the dielectric contained in the first dielectric layer and the water absorption rate of the dielectric contained in the second dielectric layer are both 0.2 or less.

[0035] [Item 10]

[0036] The structure according to any one of items 1 to 9 has a thickness of 20 μm or more and 150 mm or less.

[0037] [Item 11]

[0038] The structure according to any one of items 1 to 10, wherein the polarization directions of the incident wave and the transmitted wave are different when irradiated with electromagnetic waves.

[0039] [Item 12]

[0040] According to any one of items 1 to 11, the area of ​​the second metal pattern layer is 0.09 mm². 2 Above 20m 2 the following.

[0041] [Item 13]

[0042] The structure according to any one of items 1 to 12, wherein the operating frequency is 0.3 GHz or more and 10 THz or less.

[0043] [Item 14]

[0044] An electromagnetic wave transceiver system comprising the structure described in any one of claims 1 to 13 and an electromagnetic wave oscillation antenna.

[0045] Invention Effects

[0046] According to one aspect of the present invention, it is possible to provide a structure having a thin-layer structure and high electromagnetic wave control efficiency. Attached Figure Description

[0047] Figure 1 The diagram illustrates the structures fabricated in Examples 1 and 2.

[0048] Figure 2 This is a diagram illustrating the second metal pattern in the structure fabricated in Example 1.

[0049] Figure 3 This is a diagram illustrating the second metal pattern in the structure fabricated in Example 2.

[0050] Figure 4 It shows that Figure 3 The graph illustrates the relationship between the shape of the second metal pattern in the structure fabricated in Embodiment 2 and the phase of the transmitted wave as the length L changes. Here, the numbers preceding the hyphens on the horizontal axis indicate... Figure 3 The shape in the diagram is represented by the number after the hyphen, which indicates L, and the vertical axis represents the phase of the transmitted wave.

[0051] Figure 5 This is a diagram showing the second metal pattern layer, which is a square pattern with one side approximately 50 mm in length.

[0052] Figure 6 This is a diagram illustrating the measurement of the electromagnetic wave intensity of an oscillator.

[0053] Figure 7 This is a diagram illustrating the measurement of the electromagnetic wave intensity of the structure fabricated in Example 2.

[0054] Figure 8 This is a diagram illustrating the measurement of the electromagnetic wave collimation capability of the structure fabricated in Example 2.

[0055] Figure 9 The graph shows the results of measuring the electromagnetic wave intensity when the structure made in Example 2 is placed and when the structure is not placed.

[0056] Figure 10 This is a diagram illustrating the measurement of the electromagnetic wave intensity of the structure fabricated in Example 2.

[0057] Figure 11 Yes Figure 10 The graph illustrates the intensity distribution of electromagnetic waves measured in the medium.

[0058] Figure 12 This is a diagram illustrating the second metal pattern layer in the structure fabricated in Example 11.

[0059] Figure 13 This is a diagram illustrating the second metal pattern layer in the structure fabricated in Example 12.

[0060] Figure 14 This is a diagram illustrating the second metal pattern layer in the structure fabricated in Example 13.

[0061] Figure 15 This is a diagram illustrating the second metal pattern in the structure fabricated in Example 2.

[0062] Figure 16A This figure illustrates a structure according to another embodiment, namely a structure in which a metal compound layer is in contact with the boundary surface of a first dielectric layer and / or a second dielectric layer.

[0063] Figure 16B This diagram illustrates a structure of another embodiment, namely a structure having a layer of metal compound inside the metaatoms.

[0064] Figure 17 This is a schematic perspective partial cross-sectional view of the structure according to another embodiment.

[0065] Figure 18 This is a diagram illustrating an electromagnetic wave transceiver system. Detailed Implementation

[0066] Hereinafter, exemplary embodiments of the present invention (sometimes referred to as these embodiments) will be described, but the present invention is not limited to these embodiments.

[0067] In this disclosure, various measurements are performed based on the methods described in the specification, particularly the methods described in the embodiments. In this specification, the upper or lower limit of a phased numerical range can be replaced by the upper or lower limit of another corresponding phased numerical range, particularly by the corresponding values ​​described in the embodiments. Furthermore, in this specification, "process" is not only an independent process, but is also included in this terminology as long as the function of the process can be achieved, even when it cannot be clearly distinguished from other processes. The structures (scale, shape, length, etc.) shown in the accompanying drawings are sometimes exaggerated for further clarity.

[0068] The structure of this embodiment sequentially comprises a first metal pattern layer, a first dielectric layer, a second metal pattern layer, a second dielectric layer, and a third metal pattern layer.

[0069] [Metal Pattern Layer]

[0070] The metal patterned layer of this embodiment may have a layer structure, and in particular, may constitute at least one layer in a series of metal patterned layers. The metal patterned layer may be disposed at a location in contact with the dielectric layer described later. The metal patterned layer does not necessarily have to be disposed on the surface of the dielectric layer, but may also be disposed (in one embodiment, embedded) within the dielectric layer.

[0071] In a typical embodiment, the metal pattern layer includes a first metal pattern layer, a second metal pattern layer separated from the first dielectric layer (described later), and a third metal pattern layer separated from the second dielectric layer (described later). Furthermore, the first metal pattern layer is in contact with the first dielectric layer, the first dielectric layer with the second metal pattern layer, the second metal pattern layer with the second dielectric layer, and the second dielectric layer with the third metal pattern layer. In this case, the first metal pattern layer, the second metal pattern layer, and the third metal pattern layer can be treated as the aforementioned metal pattern layer.

[0072] The shape of the metal patterned layer in this embodiment is not particularly limited; for example, it can be a polyhedron. The surface of the metal patterned layer can be planar or curved. Additionally, the metal patterned layer can have internal voids. In one embodiment, the metal patterned layer can function as metaatoms. In this case, the size of the metal patterned layer can be appropriately designed according to the wavelength of the electromagnetic wave incident on the electromagnetic wave control element.

[0073] The incident electromagnetic wave can be a millimeter wave to a terahertz wave, with a wavelength ranging from 11 mm to 100 μm. From the perspective of efficiently exciting surface plasmons by the incident electromagnetic wave, the square root of the area of ​​the surface in contact with the dielectric layer of each metal patterned layer is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more relative to the wavelength of the incident electromagnetic wave, and preferably less than 1 time, or less than 0.7 times, or less than 0.5 times.

[0074] The metal pattern layer in this embodiment can also be periodically configured to generate a gradient in the phase shift of the electromagnetic wave emitted from the electromagnetic wave control element (e.g., the reflected wave in the case of an electromagnetic wave reflecting element). In this case, the pattern period is preferably 1.06 times or more, 1.15 times or more, or 1.74 times or more, preferably 20 times or less, 12 times or less, or 6 times or less, relative to the wavelength corresponding to the frequency of the electromagnetic wave incident on the electromagnetic wave reflecting element. According to the structure of this embodiment, by adjusting the size and period of the metal pattern layer, the reflection direction of the reflected wave at the desired frequency can be easily designed. Therefore, an electromagnetic wave reflecting element capable of abnormally reflecting electromagnetic waves in the desired direction (i.e., reflecting in a direction different from specular reflection) can be manufactured with a simple process.

[0075] (First metal pattern layer)

[0076] The first metal pattern layer in this embodiment has a slit-shaped metal pattern. The shape and size of the metal pattern are selected as needed.

[0077] The first metal pattern layer can be in contact with the first dielectric layer, or it can be separated by other layers without contact.

[0078] The width of the metal slit in the first metal pattern layer of this embodiment can be appropriately varied according to the wavelength of the irradiated electromagnetic wave. From the perspective of ease of processing, the width of the metal slit is preferably 0.005 times or more, or 0.01 times or more, or 0.05 times or more of the wavelength of the irradiated electromagnetic wave. From the perspective of improving the transmittance of the electromagnetic wave irradiating the structure, it is preferably 0.3 times or less, or 0.2 times or less, or 0.1 times or less of the wavelength of the irradiated electromagnetic wave.

[0079] From the perspective of improving the transmittance of electromagnetic waves irradiating the structure of this embodiment, the spacing between the metal slits in the first metal pattern layer of this embodiment is preferably 0.005 times or more, or 0.01 times or more, or 0.05 times or more of the wavelength of the irradiated electromagnetic waves. Similarly, it is preferably 0.3 times or less, or 0.2 times or less, or 0.1 times or less of the wavelength of the irradiated electromagnetic waves.

[0080] From the perspective of improving the transmittance of electromagnetic waves irradiating the structure of this embodiment, the thickness of the first metal pattern layer in this embodiment is preferably 50 nm or more, or 100 nm or more, or 300 nm or more. From the same perspective, it is preferably 100 μm or less, 50 μm or less, or 20 μm or less.

[0081] The first metal pattern layer in this embodiment preferably has a three-dimensional curved surface shape. In this embodiment, a three-dimensional curved surface refers to a surface that cannot be formed by deforming a plane (i.e., it is not a developable surface). From the perspective of being able to freely control the incident angle of electromagnetic waves incident on the structure, for example, improving the range of control over the direction of electromagnetic waves, the first metal pattern layer is preferably a three-dimensional curved surface shape.

[0082] The metal constituting the first metal pattern layer in this embodiment is not particularly limited, and examples include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium. From the perspective of ease of processing and improving the transmittance of electromagnetic waves, the metal constituting the first metal pattern layer in this embodiment is preferably silver, copper, gold, platinum, aluminum, nickel, and iron, more preferably silver, copper, gold, platinum, and aluminum, and even more preferably silver, copper, and aluminum.

[0083] (Second metal pattern layer)

[0084] The second metal pattern layer in this embodiment is a layer formed by configuring metal patterns from the metals constituting the second metal pattern layer. Multiple metal patterns can be configured from the metals constituting the metal pattern layer, and their shape and size can be selected as needed.

[0085] In this embodiment, the second metal pattern layer is disposed between the first metal pattern layer and the third metal pattern layer (described later), and between the first dielectric layer (described later) and the second dielectric layer (described later). The second metal pattern layer may be in contact with the first dielectric layer and the second dielectric layer, or it may be separated by other layers without contact.

[0086] The second metal patterned layer in this embodiment contains metaatoms.

[0087] In this disclosure, the area of ​​the second metal pattern layer in this embodiment refers to the area surrounding the outer perimeter of the second metal pattern layer. In one embodiment, the area surrounding the outer perimeter of the second metal pattern layer refers to the area that covers the entire second metal pattern layer and has the smallest area. The shape of the portion covering the entire second metal pattern layer can be a rectangle (e.g., rhombus, parallelogram, oblong, and square) and a circle (e.g., ellipse).

[0088] From the viewpoint that the electromagnetic waves emitted from the structure of this embodiment can cover a wide area, the area of ​​the second metal pattern layer in this embodiment is preferably 0.09 mm. 2 Above, or 0.36mm 2 Above or 9mm 2 That's all. Furthermore, from the perspective of ease of processing, the area of ​​the second metal pattern layer in this embodiment is preferably 20 μm². 2 Below, or 5m 2 Below, or 0.02m 2 Below, or 1100mm 2 Below, or 400mm 2 Below, or 110mm 2 the following.

[0089] The area of ​​the second metal pattern layer in this embodiment is preferably 0.09 mm. 2 Above 20m 2 The following, or more preferably, is 0.36mm 2 The above 5m 2 the following.

[0090] The area of ​​the second metal patterned layer in this embodiment is measured by the following method.

[0091] The characteristic length of the surface surrounding the outer periphery of the second metal pattern layer (in one embodiment, the longitudinal and transverse lengths of the second metal pattern layer, and the diameter of the second metal pattern layer) can also be used to calculate the area of ​​the second metal pattern layer by measuring the length of the structure (hereinafter referred to as the sample) fabricated in the embodiment using an optical microscope, without any particular limitation.

[0092] In one method, if the face surrounding the second metal pattern layer is a quadrilateral (e.g., a rectangle or a square), the longitudinal and transverse lengths of the second metal pattern layer are measured, and the area of ​​the second metal pattern layer is calculated by multiplying the longitudinal and transverse lengths respectively. In another method, if the face surrounding the second metal pattern layer is a quadrilateral (e.g., a parallelogram), the height and transverse length of the second metal pattern layer are measured, and the area of ​​the second metal pattern layer is calculated by multiplying the height and transverse lengths respectively. In yet another method, if the face surrounding the second metal pattern layer is a quadrilateral (e.g., a rhombus), the lengths of the two diagonals of the second metal pattern layer are measured, and the area of ​​the second metal pattern layer is calculated by multiplying the lengths of each diagonal by 2.

[0093] In another approach, if the surface surrounding the outer periphery of the second metal pattern layer is circular, the radius is determined by measuring the diameter, and the area of ​​the second metal pattern layer is obtained by multiplying π by the square of the radius.

[0094] The second metal pattern layer in this embodiment preferably has a three-dimensional curved surface shape. From the perspective of being able to freely control the incident angle of electromagnetic waves incident on the structure, and for example, improving the range of control over the direction of electromagnetic waves, the second metal pattern layer is preferably a three-dimensional curved surface shape.

[0095] [Supreme Atoms]

[0096] In this disclosure, a superatom refers to one or more metal patterns constituting the second metal pattern layer.

[0097] The shape of the metaatom in this embodiment is not particularly limited; for example, it can be a polyhedron. The metaatom may have cavities inside. The surface of the metaatom can be planar or curved.

[0098] Regarding the size of the metaatom in this embodiment, from the perspective of efficiently exciting surface plasmons by incident electromagnetic waves, the diameter of the smallest containing sphere of the metaatom is preferably 10 μm or more, or 30 μm or more, or 90 μm or more. From the above perspective, it is preferably 430 mm or less, or 200 mm or less, or 85 mm or less, or 15 mm or less, or 4 mm or less, or 2 mm or less.

[0099] The size of the metaatom in this embodiment can be appropriately designed according to the wavelength of the electromagnetic wave incident on the structure. The incident electromagnetic wave can be a microwave to a terahertz wave, with a wavelength, for example, ranging from 10 μm to 430 mm. From the perspective of efficiently exciting surface plasmons by the incident electromagnetic wave, the diameter of the smallest containing sphere of the metaatom in this embodiment is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more relative to the wavelength of the incident electromagnetic wave, and preferably less than 1 time, or less than 0.7 times, or less than 0.5 times.

[0100] From the perspective of suppressing the energy of electromagnetic waves incident on the electromagnetic wave control element from being converted into heat energy and thus attenuating, the volume resistivity of the metaatoms in this embodiment is preferably 1×10⁻⁶. -3 Ω Less than m, or 1×10 -4 Ω Less than m, or 1×10 -5 Ω Less than m, or 1×10 -6 Ω Below m.

[0101] From the perspective of efficiently exciting surface plasmons by incident electromagnetic waves, the thickness of the metaatoms in this embodiment is preferably 50 nm or more, or 100 nm or more. Similarly, the thickness of the metaatoms in this embodiment is preferably 300 μm or less, or 200 μm or less, or 100 μm or less. It should be noted that the thickness of the metaatoms is measured using the method described in the examples.

[0102] There are no particular limitations on the metals that make up the superatoms. Examples include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0103] From the perspective of minimizing the attenuation of surface plasmons excited by electromagnetic waves, the metals comprising the metaatoms in the second metal pattern layer of this embodiment preferably include silver, copper, gold, platinum, aluminum, nickel, and iron, more preferably silver, copper, gold, platinum, and aluminum, and even more preferably silver, copper, and gold. From the perspective of improving the adhesion between the metaatoms and the adjacent dielectric, and the antioxidant layer additionally provided to prevent oxidation of the metaatoms, copper is the most preferred metaatom.

[0104] In one embodiment of the present invention, the metaatom comprises a metal and carbon. Furthermore, from the viewpoint of improving the adhesion between the metaatom and the first and second dielectrics, the carbon content of the metaatom relative to the metal element (in one embodiment, the carbon / metal element concentration ratio of the metaatom) is preferably 0.05 or more, or 0.1 or more, or 0.5 or more. From the viewpoint of minimizing the attenuation of surface plasmons excited by electromagnetic waves, the carbon / metal element concentration ratio of the metaatom is 6.0 or less, or 5.5 or less, or 5.0 or less. The carbon / metal element concentration ratio of the metaatom is preferably 0.05 or more and 6.0 or less, more preferably 0.1 or more and 5.5 or less, and particularly preferably 0.5 or more and 5.0 or less.

[0105] As a method for controlling the carbon / metal elemental concentration ratio of the metaatom to the aforementioned range, one example is the method of manufacturing metaatoms by irradiating a composition in which the mixing ratio of a metal compound and an organic compound is adjusted with energy such as heat, plasma, or electromagnetic waves. The carbon / metal elemental concentration ratio of the metaatom can be determined using EDX analysis.

[0106] (Metal compound layer)

[0107] The structure of this embodiment preferably has a metal compound layer at the boundary between the metaatom and the first dielectric layer and / or the second dielectric layer. In this embodiment, having a metal compound layer at the boundary between the metaatom and the first dielectric layer and / or the second dielectric layer means that the metal compound layer is disposed between the metaatom and the first dielectric layer and / or the second dielectric layer.

[0108] Figure 16A This diagram illustrates the structure where the metal compound layer 17 is in contact with the boundary surface of the first dielectric layer 12 (not shown). Figure 16A As shown, the meta-atom 16 is in contact with the metal compound layer 17, which is disposed between the meta-atom 16 and the first dielectric layer 12 (not shown).

[0109] Furthermore, the metaatoms in this embodiment preferably have a metal compound layer inside them.

[0110] Figure 16B This diagram illustrates a structure having a metal compound layer 17 inside the superatoms 16. (See diagram for example.) Figure 16B As shown, the metal compound layer 17 is contained within the metaatoms 16.

[0111] In this embodiment, if the metal compound layer is a nitride, then the metal compound layer refers to the region where the nitrogen / metal elemental concentration ratio is 0.1 or higher in the EDX analysis; if the metal compound layer is an oxide, then the metal compound layer refers to the region where the oxygen / metal elemental concentration ratio is 0.1 or higher in the EDX analysis.

[0112] From the perspective of improving reflectivity, the thickness of the metal compound layer in this embodiment is preferably 40 nm or more, or 75 nm or more, or 100 nm or more. Similarly, from the same perspective, the thickness of the metal compound layer in this embodiment is preferably 10 μm or less, or 5 μm or less, or 1 μm or less.

[0113] It should be noted that the thickness of the metal compound layer in this embodiment was measured using the method described in the examples.

[0114] From the perspective of improving reflectivity, the proportion of the metal compound layer in the thickness of the metaatomic layer is preferably 0.01 or more, or 0.1 or more, 0.15 or more, or 0.2 or more. Similarly, it is preferably 0.5 or less, or 0.3 or less.

[0115] The metal compounds used in this embodiment are not particularly limited, and examples include oxides or nitrides of silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0116] From the perspective of its stable existence as a metal compound and its ability to be reduced to a metal with relatively little energy, copper is preferred as the metallic element constituting the metal compound layer. Similarly, copper oxide is preferred as the metal compound.

[0117] From the perspective of efficiently exciting surface plasmons by incident electromagnetic waves, it is preferable that both the metaatomic and metallic compound layers constituting this embodiment contain copper.

[0118] The metal compound layer in this embodiment preferably has a three-dimensional curved surface shape. From the perspective of being able to freely control the incident angle of electromagnetic waves incident on the structure, and for example, improving the range of control over the direction of electromagnetic waves, the metal compound layer is preferably a three-dimensional curved surface shape.

[0119] (Third metal pattern layer)

[0120] The third metal pattern layer of this embodiment has a slit-shaped metal pattern. From the viewpoint of improving the transmittance of electromagnetic waves irradiating the structure of this embodiment, the direction of the slit of the third metal pattern in this embodiment is preferably different from the direction of the slit of the first metal pattern, and more preferably the direction of the slit of the first metal pattern is orthogonal to the direction of the slit of the third metal pattern.

[0121] In this embodiment, the third metal pattern layer can be in contact with the second dielectric layer, or it can be separated from other layers without contact.

[0122] Regarding the width, spacing, thickness, and metal elements constituting the metal pattern of the third metal pattern layer in this embodiment, it is preferable to use the same method as the first metal pattern layer described above.

[0123] [Dielectric layer]

[0124] In this embodiment, the dielectric layer is disposed on the metal pattern layer, and more specifically, disposed such that at least a portion of it is in contact with the surface of the metal pattern layer. That is, the space between the metal pattern layer and the dielectric layer of this embodiment may contain, for example, an air or vacuum layer. In one embodiment, the dielectric layer has a morphology in which dielectric patterns are periodically disposed on the metal pattern layer of this embodiment (i.e., arranged regularly to form a repeating structure). Based on such a dielectric pattern, by appropriately designing the shape and size of the pattern, the degree of phase shift of the electromagnetic wave can be easily controlled, and thus an electromagnetic wave control element capable of emitting electromagnetic waves covering a wide area can be manufactured with a simple process.

[0125] The shape of the dielectric pattern can be appropriately selected as needed, including rectangles and other polygons, circles, ellipses, rings, open rings, multiple open rings, etc. The dielectric pattern can also be formed by regularly arranging recesses of these shapes in the dielectric layer of this embodiment. The size of the dielectric pattern can be appropriately designed according to the desired degree of phase shift. For example, in the case of a rectangle, in one approach, from the perspective of easily achieving the desired phase shift, the minor axis of the dielectric pattern is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more relative to the wavelength of the incident electromagnetic wave; from the above perspective, it is preferably less than 1 time, or less than 0.7 times, or less than 0.5 times.

[0126] Even when the dielectric in this embodiment is formed into a tiny dielectric pattern, a dielectric layer with few and uniform voids can be formed. Therefore, by arranging the dielectric pattern, which is finer than the wavelength of electromagnetic waves, in a two-dimensional configuration in a desired shape, it can function as a metasurface. Thus, the shape of the dielectric pattern can be any shape that those skilled in the art would understand as being able to function as a so-called metasurface.

[0127] The dielectric pattern can also be periodically configured to generate a gradient in the phase shift of the electromagnetic wave emitted from the electromagnetic wave control element (e.g., the reflected wave in the case of the electromagnetic wave reflecting element). In this case, the pattern period is preferably 1.06 times or more, or 1.15 times or more, or 1.74 times or more, preferably 20 times or less, or 12 times or less, or 6 times or less, relative to the wavelength corresponding to the frequency of the electromagnetic wave incident on the electromagnetic wave reflecting element.

[0128] (First dielectric layer)

[0129] In this embodiment, the first dielectric layer is disposed between the first metal pattern layer and the second metal pattern layer. The first dielectric layer may be in contact with the first metal pattern layer and / or the second metal pattern layer, or it may be separated by other layers without contact.

[0130] In one embodiment, the first dielectric layer comprises a dielectric.

[0131] In another embodiment, the first dielectric layer may be composed of two or more dielectric layers containing different dielectrics in terms of relative permittivity, material, water absorption rate, and thickness.

[0132] From the perspective of suppressing changes in dielectric constant and size caused by water absorption, as well as the attenuation of transmitted electromagnetic waves, the water absorption rate of the dielectrics of the first dielectric layer and the second dielectric layer (described later) is preferably 0.2 or less, or 0.15 or less, or 0.1 or less.

[0133] From the perspective of, for example, producing a desired phase shift in electromagnetic waves for electromagnetic wave control applications, the relative permittivity ε of the dielectric of the first dielectric layer... r1 Preferably, the relative permittivity ε of the dielectric material in the first dielectric layer is 2 or higher, or 2.2 or higher, or 2.4 or higher. From the perspective of reducing energy loss of electromagnetic waves, for example in applications involving electromagnetic wave control, the relative permittivity ε of the dielectric material in the first dielectric layer is... r1 Preferably, the value is 10 or less, or 5 or less, or 3 or less, or 2.8 or less.

[0134] The dielectric material contained in the first dielectric layer can be ceramic or resin.

[0135] As ceramics, examples include oxides, carbides, nitrides, borides, and fluorides of one or more elements selected from silicon, silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium.

[0136] In particular, from the perspective of ease of processing, oxides, carbides, nitrides, borides and fluorides of silicon, copper, aluminum and magnesium are preferred.

[0137] Examples of resins include polyimide (PI), liquid crystal polyester (LCP), polyesters (polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc.), polyethersulfone (PES), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyacetal (POM), polyarylate (PAR), polyamide (PA) (PA6, PA66, etc.), polyamide-imide (PAI), polyether-imide (PEI), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyphenylene sulfide (PPS), polyetherketone (PEK), polyphthalamide (PPA), polyether nitrile (PENt), polybenzimidazole (PBI), polycarbodiimide, polysiloxane, polymethacrylamide, nitrile rubber, acrylic rubber, polytetrafluoroethylene, and epoxy resins. Resins, phenolic resins, melamine resins, urea resins, polymethyl methacrylate resin (PMMA), polybutene, polypentene, ethylene-propylene copolymer, ethylene-butene-diene copolymer, polybutadiene, polyisoprene, ethylene-propylene-diene copolymer, butyl rubber, polymethylpentene (PMP), polystyrene (PS), styrene-butadiene copolymer, polyethylene (PE), polypropylene, polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polyether ether ketone (PEEK), phenolic varnish, benzocyclobutene, polyvinylphenol, polychloroprene, polyoxymethylene, polysulfone (PSF), polyphenylene sulfone resin (PPSU), cyclic olefin polymers (COP), acrylonitrile-butadiene-styrene resin (ABS), acrylonitrile-styrene resin (AS), polytetrafluoroethylene resin (PTFE), and polychlorotrifluoroethylene (PCTFE), etc.

[0138] In particular, from the perspective of reducing dielectric loss, PI, LCP, PC and m-PPE are preferred, and from the perspective of improving the adhesion to the metal pattern and reducing copper damage when the metal pattern layer is formed of copper, m-PPE is the most preferred.

[0139] The thickness of the first dielectric layer can be appropriately designed according to the wavelength of the electromagnetic wave incident on the structure. The incident electromagnetic wave can be a microwave to a terahertz wave, with a wavelength ranging from 10 μm to 430 mm.

[0140] From the perspective of increasing the transmittance of electromagnetic waves irradiating the structure, the thickness of the first dielectric layer is preferably 0.02 times or more, or 0.05 times or more, or 0.1 times or more relative to the wavelength of the incident electromagnetic wave. From the perspective of reducing dielectric loss in the dielectric, the thickness is preferably 0.5 times or less, or 0.1 times or less, or 0.05 times or less relative to the wavelength of the incident electromagnetic wave.

[0141] The first dielectric layer in this embodiment preferably has a three-dimensional curved surface shape. From the perspective of being able to freely control the incident angle of electromagnetic waves incident on the structure, and for example, improving the range of control over the direction of electromagnetic waves, the first dielectric layer is preferably a three-dimensional curved surface shape.

[0142] (Second dielectric layer)

[0143] The second dielectric layer is disposed between the second metal pattern layer and the third metal pattern layer. The second dielectric layer may be in contact with the second metal pattern layer and / or the third metal pattern layer, or it may be separated by other layers without contact.

[0144] In one embodiment, the second dielectric layer comprises a dielectric.

[0145] In another embodiment, the second dielectric layer may be composed of two or more dielectric layers containing different dielectrics in terms of relative permittivity, material, water absorption rate, and thickness.

[0146] Regarding the relative permittivity, material, water absorption rate, and thickness of the second dielectric layer, it is preferably the same as that of the first dielectric layer, but the relative permittivity of the first dielectric layer is set to ε. r1 Let the thickness of the first dielectric layer be S1 [μm], and the relative permittivity of the second dielectric layer be ε. r2 When the thickness of the second dielectric layer is set to S2 [μm], ε r2 / ε r1 The ratio of S2 / S1 is greater than 0.9 and less than 1.1. By making the relative permittivity of the first dielectric layer and the second dielectric layer, as well as the thickness of the first dielectric layer and the second dielectric layer, close to each other, the transmittance of electromagnetic waves irradiating the structure can be improved.

[0147] ε r2 / ε r1 The ratio of S2 to S1 is more preferably 0.92 or higher, and even more preferably 0.95 or higher. Additionally, ε r2 / ε r1The ratio of S2 / S1 is more preferably 1.08 or less, and even more preferably 1.05 or less.

[0148] The thicknesses S1 of the first dielectric layer and S2 of the second dielectric layer were measured as follows.

[0149] The thickness S1 of the first dielectric layer and the thickness S2 of the second dielectric layer were determined by measuring the sample using a constant pressure thickness gauge (product name PG20-A, manufactured by TECLOCK Co., Ltd.).

[0150] The relative permittivity ε of the dielectric contained in the first dielectric layer r1 The relative permittivity ε of the dielectric contained in the second dielectric layer r2 The following measurements were taken.

[0151] ε r1 and ε r2 The time waveform of the transmitted electric field when a terahertz wave passes through a dielectric was calculated using the TAS7500SL manufactured by Advantest.

[0152] The water absorption rate of the dielectrics contained in the first and second dielectric layers was determined by dry weight method according to Method A of JIS K7209 using a sample of the same size as the D1 type of ISO 294-3.

[0153] The second dielectric layer in this embodiment preferably has a three-dimensional curved surface shape. From the perspective of being able to freely control the incident angle of electromagnetic waves incident on the structure, and for example, improving the range of control over the direction of electromagnetic waves, the second dielectric layer is preferably a three-dimensional curved surface shape.

[0154] [Resin Layer]

[0155] like Figure 17 As shown, the structure 10 of this embodiment preferably has a resin layer 18 on the outer side of the first metal pattern layer 11 and the third metal pattern layer 15 of this embodiment.

[0156] Examples of resin layers used in this embodiment include silicone resins, fluororesins, butyral resins, polyurethane resins, epoxy resins, acrylic resins, modified polyesters, polyamide resins, polyolefin resins, fluorinated acrylic resins, and polyimides.

[0157] The presence of the resin layer in this embodiment prevents oxidation of the first and third metal pattern layers due to contact with oxygen in the air, thus enabling them to maintain electromagnetic wave control performance for a longer period. Furthermore, it reduces the amount of water penetrating into the structure of this embodiment and suppresses water absorption by the first and second dielectric layers, thereby preventing the reduction in adhesion between the metal pattern layer and the dielectric layer caused by dimensional changes due to water absorption.

[0158] In particular, when the dielectric layer in this embodiment is formed of a resin with low water absorption, such as modified polyphenylene ether (m-PPE), the amount of water absorbed into the dielectric layer is suppressed in combination with the effect brought about by the presence of the resin layer, and electromagnetic wave control performance can be maintained for a longer period of time.

[0159] [Structure]

[0160] The relative permittivity of the first dielectric layer is set to ε. r1 Let the thickness of the first dielectric layer be S1 [μm], and the relative permittivity of the second dielectric layer be ε. r2 When the thickness of the second dielectric layer is set to S2 [μm], ε r1 With ε r2 Let the average value be ε r When the average value of S1 and S2 is set as S[μm], the width of the metaatom is set as w[μm], the thickness of the metaatom is set as t[μm], and the wavelength of the incident electromagnetic wave is set as λ[μm], the following equation (1) is satisfied.

[0161]

[0162] Here, n is an integer greater than or equal to 0.

[0163] By satisfying the above formula (1), the transmittance increases when electromagnetic waves are irradiated onto the structure of this embodiment.

[0164] ε r1 With ε r2 The average value ε r For the arithmetic mean, through (ε) r1 +ε r2 ÷ 2 to find the answer.

[0165] The average value S of S1 and S2 is the arithmetic mean, which can be obtained by (S1+S2)÷2.

[0166] The width w of the second metal pattern layer is determined by obtaining a microscope image of the sample taken using a microscope (product name ECLIPSE LV-100, manufactured by Nikon Corporation) and measuring its length.

[0167] The thickness t of the second metal patterned layer was determined by measuring a cross-sectional image of the sample taken using an electron microscope (product name S4800, manufactured by Hitachi High Technology Co., Ltd.).

[0168] It should be noted that the magnification and other conditions when taking pictures with a microscope can be adjusted appropriately according to the sample for which the width and thickness of the second metal pattern layer are being measured.

[0169] The wavelength λ of the electromagnetic wave incident on the structure is determined by measuring it using a spectrometer (product name TAS7500SL, manufactured by Advantest Co., Ltd.).

[0170] In this embodiment, the structure preferably has different polarization directions for the incident wave and the transmitted wave when irradiated with electromagnetic waves. As a method to make the polarization direction of the transmitted wave different from that of the incident wave, if the slit direction of the first metal pattern layer is not parallel to the slit direction of the third metal pattern layer, the transmittance of the structure can be improved.

[0171] The structure in this embodiment is preferably such that the transmitted wave is focused or collimated when irradiated with electromagnetic waves.

[0172] From the perspective of improving transmittance, the thickness of the structure in this embodiment is preferably 20 μm or more and 150 mm or less. More preferably, the thickness of the structure in this embodiment is 50 μm or more, and even more preferably 100 μm or more. Furthermore, the thickness of the structure in this embodiment is more preferably 100 mm or less, and even more preferably 50 mm or less.

[0173] The thickness of the structure in this embodiment was measured using the following method.

[0174] The thickness of the structure was determined by measuring the sample using a constant pressure thickness gauge (product name PG20-A, manufactured by TECLOCK Co., Ltd.).

[0175] The structure in this embodiment is preferably a structure with a thin-layer structure and high electromagnetic wave control efficiency. In this disclosure, a structure having a thin-layer structure means that the total thickness of the layers constituting the structure of this embodiment (in one embodiment, a first metal pattern layer, a first dielectric layer, a second metal pattern layer, a second dielectric layer, and a third metal pattern layer) is 10 times or less the wavelength of the electromagnetic wave, preferably 5 times or less, and more preferably 1 time or less.

[0176] The total thickness of the layers constituting the structure of this embodiment is determined by the following method.

[0177] (1) The thickness S1 of the first dielectric layer and the thickness S2 of the second dielectric layer are determined by measuring the sample using a constant pressure thickness gauge (product name PG20-A, manufactured by TECLOCK Co., Ltd.).

[0178] (2) The thicknesses of the first metal pattern layer, the second metal pattern layer and the third metal pattern layer were determined by measuring the cross-sectional images of the sample taken using an electron microscope (product name S4800, manufactured by Hitachi High Technology Co., Ltd.).

[0179] The sum of the thicknesses of each layer obtained in (1) and (2) above is taken as the total thickness of the layers constituting the structure of this embodiment.

[0180] In this disclosure, high electromagnetic wave control efficiency of the structure refers to an electromagnetic wave transmittance of 50% or higher. The electromagnetic wave transmittance is expressed as (transmitted electromagnetic wave / incident electromagnetic wave) × 100. It should be noted that the transmitted and incident electromagnetic waves are measured using the methods described in the embodiments.

[0181] The structure disclosed herein can be applied to antennas and reflectors, etc. Furthermore, the structure disclosed herein can be suitably used as a constituent material for antennas and reflectors.

[0182] Even when the structure of this embodiment is formed into a dielectric pattern of minute size, it can form a dielectric layer with few and uniform gaps. Therefore, by arranging the dielectric pattern, which is finer than the wavelength of electromagnetic waves, in a two-dimensional configuration in a desired shape, it can function as a metasurface. Thus, the structure of this embodiment is suitable for use as a metasurface lens incorporating the structure.

[0183] (Operating frequency)

[0184] The operating frequency of the structure and metasurface lens in this embodiment can be in the microwave to terahertz band. From the perspective of suitability for high-speed communication applications, the operating frequency of the structure and metasurface lens in this embodiment is preferably 0.3 GHz or higher, or 0.7 GHz or higher, or 1.5 GHz or higher, or 3.6 GHz or higher, or 27 GHz or higher, or 92 GHz or higher, or 152 GHz or higher, or 287 GHz or higher. From the perspective of suppressing electromagnetic wave attenuation, the operating frequency of the structure and metasurface lens in this embodiment is preferably 10 THz or lower, or 5 THz or lower, or 1 THz or lower.

[0185] The operating frequency of the structure and metasurface lens in this embodiment is preferably 0.3 GHz or higher and 10 THz or lower, more preferably 0.7 GHz or higher and 5 THz or lower.

[0186] Electromagnetic wave transceiver system

[0187] One aspect of the present invention provides an electromagnetic wave transceiver system, which includes a metasurface lens and an electromagnetic wave oscillating antenna as described in this embodiment. Another aspect of the present invention provides an electromagnetic wave transceiver system 25, which includes a structure 10 as described in this embodiment and an electromagnetic wave oscillating antenna 23. Radio waves oscillated by the electromagnetic wave oscillating antenna 23 are reflected by the structure 10 and oscillated as transmitted radio waves W1 to an information terminal 24. The information terminal 24 oscillates the oscillated radio waves back to the structure 10 as received radio waves W2. The type and shape of the electromagnetic wave oscillating antenna are not particularly limited and can be appropriately selected according to the purpose. For example, a microstrip antenna can be used as an electromagnetic wave oscillating antenna.

[0188] <Manufacturing Methods of Structures>

[0189] The manufacturing method of the structure in this embodiment includes a process of forming a metal pattern layer on the surface of a dielectric layer.

[0190] [Process for forming the metallic pattern layer]

[0191] In this process, a metal pattern layer is formed on the surface of the dielectric layer. Examples of methods for forming the metal pattern layer include printing a composition containing a metal compound onto the surface of the dielectric layer (printing method), vapor depositing a metal pattern onto the surface of the dielectric layer (vapor deposition method), and pressing the dielectric layer and the metal pattern layer together using a rolling mill (pressing method).

[0192] According to the printing method, a dielectric layer can be formed directly and with high precision on a metal pattern layer, thus improving productivity compared to methods such as development and etching using masks. Furthermore, while vapor deposition requires a decompression process, the printing method does not, resulting in a cost advantage.

[0193] From the perspective that even with a large surface area of ​​the metal pattern layer, the dielectric layer can be uniformly coated with a low-cost process, the printing method is preferred.

[0194] In printing, a composition containing a metal compound can be coated onto a portion or all of a dielectric layer to form a film. The composition containing the metal compound used in printing can be a composition whose viscosity has been adjusted to have the desired flowability, or it can be used directly or dispersed in a dispersion medium.

[0195] Specific coating methods used in printing include aerosol printing, screen printing, direct gravure printing, gravure offset printing, flexographic printing, flatbed offset printing, and distributor painting. Coating mechanisms include die coating, spin coating, slot coating, bar coating, doctor blade coating, spray coating, and dip coating. The coating film can be dried as needed through a drying process.

[0196] In the pressing method, an adhesive layer can be sandwiched between the metal pattern layer and the dielectric layer and pressed using a rolling mill. In this case, the metal pattern layer and the dielectric layer can be held more firmly.

[0197] In one approach, a metallic patterned layer is formed on and / or within a dielectric layer by irradiating it with energy. Examples of methods for forming a metallic patterned layer by energy irradiation include thermal sintering, plasma sintering, and photo-sintering.

[0198] In the thermal firing method, a portion of the metal compound on and / or within the dielectric layer is reduced to metal using a firing furnace. In this method, a heat-reflective masking film depicting a pattern corresponding to the shape of a target metal pattern is disposed on the dielectric layer, and patterning is achieved by irradiating the heat-reflective masking film with infrared light. This allows the formation of a laminated structure consisting of a metal pattern layer, a dielectric layer, and a metal pattern layer arranged sequentially.

[0199] To sinter the metal, a coating of a metal compound composition is heat-fired at a temperature of 100°C or higher, preferably 150°C or higher, and more preferably 200°C or higher. From a process efficiency perspective, in one approach, the heat-firing temperature can be below 1000°C, below 600°C, or below 400°C. During heat-firing, since the dielectric layer is easily affected by oxygen, it is preferable to heat-fire it in a non-oxidizing atmosphere. A non-oxidizing atmosphere refers to an atmosphere that does not contain oxidizing gases such as oxygen, for example, an atmosphere filled with inert gases such as nitrogen, argon, helium, or neon.

[0200] The reduction of metal compounds is achieved by the contribution of organic matter present on and / or within the dielectric layer, but when reduction is difficult to achieve using only organic matter, it is preferable to perform hot firing in a reducing atmosphere.

[0201] In addition, a reducing atmosphere refers to an atmosphere containing reducing gases such as hydrogen and carbon monoxide; it is an atmosphere filled only with reducing gases or a mixture of reducing and inert gases. These gases can be filled into a firing furnace, and the dielectric layer can be fired while the gas flows continuously in a closed system. Firing can be carried out under any atmosphere, including atmospheric pressure, pressurized atmosphere, and depressurized atmosphere.

[0202] In plasma sintering, a plasma-absorbing material (such as glass or resin) with a pattern corresponding to the shape of a target metal pattern is placed on a dielectric layer, and plasma is irradiated onto the plasma-absorbing material to form a pattern. This allows the formation of a laminated structure consisting of a metal pattern layer, a dielectric layer, and another metal pattern layer arranged sequentially.

[0203] Compared to thermal firing, plasma firing can be performed at lower temperatures, which is advantageous when using dielectrics with low heat resistance. Furthermore, plasma firing can remove organic matter and oxide films from the patterned surface using plasma, thus ensuring good weldability, for example, when further welding electromagnetic wave control components.

[0204] Specifically, a reducing gas, or a mixture of a reducing gas and an inert gas, flows through a chamber, and plasma is generated by microwaves. The resulting active species are used as a heat source for reduction or sintering to form a metallic pattern. Hydrogen, etc., can be used as the reducing gas, and nitrogen, helium, argon, etc., can be used as the inert gas. They can be used alone or mixed in any proportion. In addition, two or more inert gas components can be mixed.

[0205] In plasma sintering, the deactivation of active species is particularly pronounced in the metal portion, which is then selectively heated. Metal compounds on and / or within the dielectric layer transform into metals as sintering progresses, promoting heating only in the metal patterned portion. Furthermore, if organic matter remains in the metal pattern, it hinders sintering, and the resistivity of the metal pattern tends to increase; however, plasma sintering is highly effective at removing organic matter from metal patterns.

[0206] Plasma firing allows for the adjustment of microwave input power, introduced gas flow rate, chamber pressure, distance from the plasma source to the sample, sample temperature, and processing time. By adjusting these parameters, the processing intensity can be altered. Therefore, optimizing these adjustments can yield metal patterns of various thicknesses. However, the optimal conditions vary depending on the type and / or amount of metal compound particles and non-volatile organic compounds on and / or within the dielectric layer, and can therefore be adjusted according to the desired outcome.

[0207] In photolithography, light irradiation is used as the energy source. Flash methods using xenon discharge tubes or lasers can be employed as the light source. These methods involve short-duration exposure to high-intensity light, rapidly raising the temperature of the dielectric layer to a high temperature for firing. This process reduces, sintersulates, integrates, and decomposes organic matter in the coating layer of the metal compound composition, forming a metallic pattern. In photolithography using laser irradiation, firing and patterning can be achieved in a single step by irradiating the coating layer of the metal compound composition with a laser.

[0208] The flash method refers to the instantaneous discharge of the charge stored in a capacitor using a xenon discharge tube. This method generates a large amount of pulsed light, which irradiates a coating layer containing a metal compound, instantly heating the metal precursor on and / or within the dielectric layer to a high temperature, causing it to transform into a metallic pattern. The exposure can be adjusted by light intensity, irradiation time, irradiation interval, and number of exposures.

[0209] Although the light source is different, the same effect as flash lighting can be achieved using a laser light source. In the case of a laser, in addition to adjusting the flash pattern, there is also freedom in wavelength selection; the emission wavelength can be selected by considering the light absorption wavelength of the coating layer containing the metal compound. Furthermore, exposure can be performed by beam scanning, allowing for easy adjustment of the exposure range, such as selecting exposure of the entire coating layer or partial exposure.

[0210] As for the types of lasers, YAG (yttrium aluminum garnet) lasers, YVO (yttrium vanadate) lasers, Yb (ytterbium) lasers, semiconductor (GaAs, GaAlAs, GaInAs) lasers, and carbon dioxide lasers can be used. Not only can the fundamental wave be used, but higher harmonics can also be extracted as needed.

[0211] Especially when using lasers, the emission wavelength is preferably between 300 nm and 1500 nm, for example, preferably 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, 1056 nm, etc. From the absorption region of the coating layer of the metal compound composition, laser wavelengths of 355 nm, 405 nm, 445 nm, 450 nm, and / or 532 nm are particularly preferred. By using lasers, desired patterns can be created three-dimensionally and freely.

[0212] By selecting the wavelengths described above, desired voids can be formed, making it easy to fabricate metal-containing films with the desired porosity. The porosity of the metal-containing film can be controlled by adjusting the output power and speed of the laser irradiating the coating film of the metal-containing compound composition. For example, slowing down the laser scanning speed helps to reduce the porosity.

[0213] Selective laser irradiation can be achieved, for example, by irradiating a coating film of a metal compound composition through a mask in a laser manner, or by directly drawing a desired pattern on the coating film by scanning a laser beam in a laser manner. The irradiated surface can be planar or non-planar, for example, it can be a shell with a three-dimensional substrate.

[0214] The exposure amount can be adjusted by the laser intensity, irradiation time, laser irradiation interval, and number of exposures. In one embodiment, preferably, in the laser-irradiated area of ​​the coating film containing the metal compound composition, a portion of the coating film remains as a metal compound layer at the boundary with the dielectric layer. The metal compound layer functions as a dielectric, thus improving transmittance.

[0215] (Cleaning process)

[0216] After laser irradiation, the unburned areas can be cleaned using a suitable cleaning solution. In this case, only the burned areas remain on the dielectric layer. Alternatively, a cleaning process can be omitted, leaving the unburned areas remaining along with the burned areas.

[0217] As a cleaning fluid used during cleaning, a solvent that disperses or dissolves metal compounds (such as copper oxide) can be used.

[0218] Specific examples include water, propylene glycol monomethyl ether acetate, 3-methoxy-3-methyl-butyl acetate, ethoxyethyl propionate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, ethylene glycol butyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, ethylene glycol, 1,2-propanediol, 1,3-butanediol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propanediol, glycerol, ethylene glycol monohexyl ether, diethylene glycol... Alcohol monoethyl ether, diethylene glycol monobutyl ether, ethylene glycol monobutyl acetate, diethylene glycol monoethyl ether acetate, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, 2-butanol, tert-butanol, n-pentanol, isopentanol, 2-methylbutanol, 2-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, 1-hexanol, 2-hexanol, 2-ethylbutanol, 1-heptanol, 2-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, 2-octanol, n-nonanol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, diacetone alcohol, and acetone, etc.

[0219] Especially when the coating layer of a composition containing a metal compound contains a dispersant, the aforementioned solvent is preferred as it effectively washes away the metal precursor. Water, ethanol, butanol, isopropanol, and acetone are particularly preferred solvents. It should be noted that a dispersant may be added to the aforementioned cleaning solution. A phosphorus-containing organic compound is preferred as the dispersant.

[0220] (Any plating process)

[0221] It can perform a plating process on metal patterns after laser irradiation.

[0222] The metal-containing film after the laser irradiation process preferably has a porosity of 0.5% by volume or more. By setting this porosity, the plating solution can easily penetrate in subsequent plating processes, resulting in good adhesion and thus good bonding. More preferably, the porosity is 0.7% by volume or more, more preferably 1.0% by volume or more, more preferably 1.5% by volume or more, more preferably 2.0% by volume or more, and more preferably 2.5% by volume or more. Furthermore, from the perspective of the adhesion between the copper-containing film and the substrate, the porosity is preferably 60% by volume or less, more preferably 58% by volume or less, more preferably 55% by volume or less, more preferably 53% by volume or less, and more preferably 51% by volume or less.

[0223] (Degreasing process)

[0224] In one embodiment, the method disclosed herein may further include a degreasing step of degreasing the metal-containing film. Examples of degreasing methods include UV degreasing and wet degreasing. The degreasing step accelerates the growth rate of subsequent plating, increasing productivity. Furthermore, this step helps reduce the porosity of the plated metal pattern.

[0225] From the perspective of the interlayer tightness of the structure, the degreasing process is preferably carried out by immersing the structure in a degreasing solution containing an amino compound.

[0226] Examples of amino-containing compounds include amino acids such as alanine, arginine, asparagine, cysteine, glutamine, glycine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, and valine; alkylamines such as methylamine, dimethylamine, ethylamine, trimethylamine, diethylamine, triethylamine, propylamine, isopropylamine, and diisopropylamine; alkanolamines such as 2-aminoethanol, diethanolamine, triethanolamine, N-methylethanolamine, and N,N-dimethylethanolamine; polyamines such as ethylenediamine, diethylenetriamine, tetraethylenepentamine, tri(hydroxymethyl)aminomethane, m-phenylenediamine, p-phenylenediamine, and 1,3-bis(aminomethyl)cyclohexane; aminosulfonic acids such as taurine; aminothiols such as 2-aminoethanethiol; and nitrogen-containing heterocyclic compounds such as 3-pyridinemethylamine and 3-pyridinemethanol. From the perspective of promoting the growth rate of the coating, 2-aminoethanol is particularly preferred.

[0227] Degreasing solutions can be commercially available products. Specifically, examples include ALC-009 from Uemura Industries, Ltd. (which contains 2-aminoethanol as an amino compound) and Cleaner Securigant 902 from Atotech Japan Co., Ltd. (which contains 2-aminoethanol as an amino compound).

[0228] Regarding the concentration of the amino-containing compound in the degreasing solution, from the perspective of removing substances that hinder the plating reaction, it is preferably 5 mmol / L or more, more preferably 10 mmol / L or more, and even more preferably 20 mmol / L or more. Furthermore, from the perspective of promoting the plating reaction, the concentration of the amino-containing compound in the degreasing solution is preferably 100 mmol / L or less, more preferably 90 mmol / L or less, and even more preferably 80 mmol / L.

[0229] Regarding the immersion time of the structure in the degreasing solution, from the perspective of promoting the growth rate of the plating, it is preferably 1 minute or more, more preferably 2 minutes or more. Furthermore, from the perspective of reducing damage to the dielectric, the immersion time of the structure in the degreasing solution is preferably 15 minutes or less, more preferably 10 minutes or less. From the perspective of uniform degreasing, immersion under stirring is preferred.

[0230] To enhance the growth rate promotion effect of the plating, the immersion temperature is preferably 15°C or higher, more preferably 30°C or higher, and even more preferably 40°C or higher. Furthermore, from the perspective of reducing damage to the dielectric, the immersion temperature is preferably 70°C or lower, more preferably 60°C or lower.

[0231] After the degreasing process, the structure is preferably cleaned with a cleaning solution. The cleaning solution is preferably water. The temperature of the cleaning solution is preferably 15°C or higher, more preferably 20°C or higher. Furthermore, from the perspective of reducing damage to the dielectric, the temperature of the cleaning solution is preferably 70°C or lower, more preferably 60°C or lower.

[0232] It is preferable to perform the plating process after cleaning the structure.

[0233] <Plating Process>

[0234] In this process, the metal-containing film, whether or not it has undergone a degreasing process, is plated. By performing electrolytic plating or electroless plating on the metal-containing film (in one way, a metal pattern layer) of the structure obtained as described above, a metal pattern layer with a desired plating layer (e.g., a copper plating layer) is obtained.

[0235] In one embodiment, the plating is electroless plating. In another embodiment, electroless plating of the metal-containing film easily improves conductivity. Electroless plating allows the formation of a metal pattern layer consisting of a metal compound layer and a plating layer. Electroless plating readily forms thick metal pattern layers, making it particularly advantageous when manufacturing structures for applications requiring high current. In one embodiment, electroless plating is preferred from the perspective of broad applicability to patterns, especially for patterned metal patterns created using lasers.

[0236] Electroless plating can utilize common electroless plating methods. For example, it can be performed in conjunction with degreasing or cleaning processes. The plating bath can be, for example, a plating solution containing copper ions and a reducing agent. By immersing the structure in the plating solution while simultaneously bubbling air, the copper ions in the solution are reduced, and copper precipitates onto the surface of the reduced copper layer, forming a copper plating layer.

[0237] As an electroless plating bath, plating solutions containing, for example, CuSO4 as a copper ion source, EDTA (ethylenediaminetetraacetic acid) or Rochelle salt as a complexing agent, and formaldehyde (CH2O), potassium tetrahydrogenate, dimethylamine borane, glyoxylic acid or hypophosphino acid as a reducing agent can be used.

[0238] Commercially available plating solutions include Thru-cup PEA-6 and Thru-cup ELC-SP from Uemura Industries, Ltd.; Melplate CU-390 and Melplate CU-5100P from Meltex Corporation; OPC Copper HFS, OPC Copper NCA, and ATS ADD COPPER IW from Okuno Pharmaceutical Industries, Ltd.; CUPOSIT328 and C4500 from Rohmand Haas Corporation; Atotech MVTP1 and PrintganthUPlus from Atotech Corporation; and Cu-150 and Cu-510 from MacDermid Corporation of Japan.

[0239] Electroless plating solutions are used in electroless plating. EDTA (ethylenediaminetetraacetic acid) is preferably included in the electroless plating solution. EDTA acts as a complexing agent, forming highly stable complexes with copper ions. Therefore, it is believed to suppress side reactions in the plating bath, stabilizing the plating bath and thus promoting uniform plating deposition, which helps prevent coating peeling. This contributes to the fabrication of structures with excellent interlayer adhesion. Furthermore, since EDTA is stable in high-temperature solutions, it also helps to accelerate the plating process.

[0240] The plating bath used for electroless plating may further contain surfactants.

[0241] From the perspective of fully utilizing the advantages brought by EDTA, the amount of EDTA in the electroless plating solution is preferably 7 g / L or more, or 10 g / L or more, or 15 g / L or more. From the perspective of reducing impurities in the plating precipitates and reducing resistance, it is preferably 50 g / L or less, or 45 g / L or less, or 40 g / L or less.

[0242] Furthermore, the temperature of the electroless plating bath is preferably 25–80°C, and more preferably 30–70°C or 35–65°C, as faster plating growth can be expected. The plating time is preferably 5–60 minutes, more preferably 5–50 minutes, and even more preferably 10–40 minutes.

[0243] Electroless plating is preferably performed using a plating solution with a copper concentration in the range of 1.5 g / L to 5.0 g / L. To improve the plating speed, a concentration of 1.5 g / L or higher is preferred; from the perspective of the uniformity of the plating film, a concentration of 5.0 g / L or lower is preferred. The copper concentration is further preferably 1.5 g / L to 4.0 g / L, further preferably 1.8 g / L to 3.5 g / L, and further preferably 2.0 g / L to 3.0 g / L.

[0244] In one approach, electroplating can be performed after electroless plating. Electroplating can utilize common electroplating methods. For example, electrodes and a metal patterned layer, the object of plating, are placed in a solution (plating bath) containing metal ions (e.g., copper ions). Then, a direct current is applied between the electrodes and the metal patterned layer by an external direct current power supply. In another approach, current can be applied to the metal patterned layer by connecting a clamp (e.g., a clip) connected to one of the electrodes of the external direct current power supply to the metal patterned layer on the dielectric layer. As a result, metal is deposited on the surface of the metal patterned layer on the dielectric layer through the reduction of metal ions, forming a plated metal layer.

[0245] For example, copper sulfate baths, copper fluoroborate baths, copper cyanide baths, and copper pyrophosphate baths can be used as electroplating baths. From the perspectives of safety and productivity, copper sulfate baths and copper pyrophosphate baths are preferred.

[0246] As a copper sulfate plating bath, a sulfuric acidic copper sulfate plating bath containing copper sulfate pentahydrate, sulfuric acid, and chlorine can be suitably used, for example. The concentration of copper sulfate pentahydrate in the copper sulfate plating bath is preferably 50 g / L or more, or 100 g / L or more, preferably 300 g / L or less, or 200 g / L or less. The concentration of sulfuric acid is preferably 40 g / L or more, or 80 g / L or more, preferably 160 g / L or less, or 120 g / L or less. The solvent in the plating bath is usually water.

[0247] The temperature of the plating bath is preferably above 20°C or 30°C, and more preferably below 60°C or 50°C. The current density during electrolytic treatment is preferably 1 A / dm³. 2 Above, or 2A / dm 2 The above is preferably 15A / dm. 2 Below, or 10A / dm 2 the following.

[0248] The copper pyrophosphate plating bath is preferably a plating bath containing copper pyrophosphate and potassium pyrophosphate. The concentration of copper pyrophosphate in the copper pyrophosphate plating bath is preferably 60 g / L or more, or 70 g / L or more, preferably 110 g / L or less, or 90 g / L or less. The concentration of potassium pyrophosphate is preferably 240 g / L or more, or 300 g / L or more, preferably 470 g / L or less, or 400 g / L or less.

[0249] The solvent in the plating bath is typically water. The pH of the plating bath is preferably 8.0 or higher, or 8.2 or higher, and preferably below 9.0 or 8.8. Ammonia or similar substances can be added to adjust the pH. The temperature of the plating bath is preferably 20°C or higher, or 30°C or higher, and preferably below 60°C or 50°C. The current density during electrolytic treatment is preferably 0.5 A / dm³. 2Above, or 1A / dm 2 The above is preferably 10A / dm. 2 Below, or 7A / dm 2 the following.

[0250] The plating bath used for electroplating may further contain surfactants.

[0251] After the plating process, it is preferable to clean the structure with a cleaning solution. The cleaning solution is preferably water. The temperature of the cleaning solution is preferably 15°C or higher, more preferably 20°C or higher. In addition, from the viewpoint of reducing damage to the dielectric, it is preferably 70°C or lower, more preferably 60°C or lower.

[0252] After the plating process, it is preferable that the porosity of the metal-containing film formed by the metal patterning process is reduced by 0.9% or more by volume. This results in better adhesion between the metal-containing film formed by laser burning and the plating layer. More preferably, the reduction rate is 1.0% or more by volume, more preferably 1.2% or more by volume, more preferably 1.5% or more by volume, and more preferably 2.0% or more by volume. From the perspective of ease of metal-containing film formation, the reduction rate can be, for example, 60% or less by volume, 55% or less by volume, or 50% or less by volume.

[0253] From the perspective of the efficient interaction between the metal pattern and electromagnetic waves, the thickness of the plating layer (in one embodiment, a copper plating layer) is preferably 1 μm or more and 100 μm or less, more preferably 1 μm or more and 50 μm or less, and even more preferably 2 μm or more and 30 μm or less.

[0254] Example

[0255] The present invention will be further illustrated by the following embodiments, but the present invention is not limited to these embodiments.

[0256] [Methods for determining physical properties]

[0257] The thickness of the layers constituting the structures made in Examples 1-12 and Comparative Example 1 was measured using the following method.

[0258] The thicknesses of the first dielectric layer and the second dielectric layer were determined by measuring the sample using a constant pressure thickness gauge (product name PG20-A, manufactured by TECLOCK Co., Ltd.).

[0259] The thicknesses of the first metal pattern layer, the second metal pattern layer, the third metal pattern layer, and the metaatomic atoms were determined by measuring microscopic images of the sample cross-section taken using an electron microscope (product name S4800, manufactured by Hitachi High Technology Co., Ltd.).

[0260] Regarding the thickness of the metal compound layer inside the metaatoms of the second metal pattern layer, after the structure was bonded to epoxy resin, a cross-section was processed using a FIB device (product name Ethos NX5000, manufactured by Hitachi High Technology Co., Ltd.) to enable cross-sectional analysis using SEM. Then, the magnification was set according to the thickness of the metaatoms within the field of view, and the elemental composition within this range was analyzed using an EDX device (product name S4800, manufactured by Hitachi High Technology Co., Ltd.) at an accelerating voltage of 5kV to calculate the elemental concentration.

[0261] The width w of the metaatom was determined by taking a microscopic image of the sample (product name ECLIPSE LV100, manufactured by Nikon Corporation) at 100x magnification and measuring its length.

[0262] The thickness t of the metaatomic atoms was determined by measuring the cross-sectional image of the sample obtained by taking a picture of the sample using an electron microscope (product name S4800, manufactured by Hitachi High Technology Co., Ltd.) at a magnification of 50,000.

[0263] The wavelength λ of the incident electromagnetic wave is determined by measuring it using a spectrometer (product name TAS7500SL, manufactured by Advantest Co., Ltd.).

[0264] (Relative permittivity)

[0265] The relative permittivity of the dielectric and metal compound layers was calculated using the TAS7500SL manufactured by Advantest Co., Ltd., based on the time waveform of the transmitted electric field when a 100 GHz electromagnetic wave passes through the dielectric.

[0266] (The dielectrics constituting the first and second dielectric layers)

[0267] As the dielectric of the first dielectric layer and the second dielectric layer constituting Example 1, a modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was used.

[0268] The thickness and relative permittivity of the dielectric in Example 1 were measured, and the results were a thickness of 400 μm and a relative permittivity of 2.56.

[0269] As the dielectric of the first dielectric layer and the second dielectric layer constituting Example 2, a modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) is used.

[0270] The thickness and relative permittivity of the dielectric in Example 2 were measured, and the results were a thickness of 1510 μm and a relative permittivity of 2.56.

[0271] As the dielectrics constituting the first and second dielectric layers of Example 3, polycarbonate resin sheets (product name EXL9330, manufactured by SABIC) are used.

[0272] The thickness and relative permittivity of the dielectric in Example 3 were measured, and the results were a thickness of 1500 μm and a relative permittivity of 2.80.

[0273] As the dielectric of the first dielectric layer and the second dielectric layer constituting Example 4, a polypropylene resin sheet (product name NOVATEC PP MG03BD, manufactured by Japan Polypropylene Co., Ltd.) was used.

[0274] The thickness and relative permittivity of the dielectric in Example 4 were measured, and the results were a thickness of 1500 μm and a relative permittivity of 2.20.

[0275] (Seamless fit)

[0276] The adhesion between the dielectric and the metal pattern is evaluated by the cross-cutting method according to JIS K-5600-5-6.

[0277] With the cutting blade perpendicular to the metal pattern on the dielectric layer, make six cuts. Change the direction by 90° and make six more cuts perpendicular to the original. Take approximately 75mm of adhesive tape (NICHIBAN No. 405) and apply it to the gridded sections of the metal pattern. Within 5 minutes of applying the tape, pull it off at an angle of approximately 60° for 0.5 to 1.0 seconds. Evaluate the peeling of the metal pattern according to the classification described in JIS, using six levels from 0 to 5.

[0278] If it is category 0, category 1 or category 2, it can be appropriately used as the structure of this embodiment.

[0279] [Example 1]

[0280] (Design of electromagnetic wave control components)

[0281] Figure 1 This is a diagram illustrating the structure fabricated in Example 1. Figure 1 The left figure is a schematic perspective view of the structure fabricated in Example 1. Figure 1 The right figure is a perspective cross-sectional view of the structure fabricated in Example 1. Additionally, Figure 2 This is a diagram illustrating the metal pattern in the structure fabricated in Example 1.

[0282] Reference Figure 1 and 2The following structure was designed: a first dielectric layer 12 (400 μm thick and with a relative permittivity of 2.56) was disposed on a slit-shaped first metal patterned layer 11 (copper, 300 nm thick, 100 μm wide, and 100 μm slit spacing), and a second metal patterned layer 13 (300 nm thick, such as...) was disposed on top of it. Figure 2 As shown, a U-shaped copper structure (750 μm long and 400 μm wide) is regularly arranged in repeating units with a longitudinal period of 1 mm and a transverse period of 1 mm. A second dielectric layer 14 (400 μm thick and 2.56 relative permittivity) is disposed on the pattern. A slit-shaped third metal pattern layer 15 (copper, 300 nm thick, 100 μm wide, and 100 μm slit spacing) is disposed on the pattern layer 15, orthogonal to the first metal pattern layer 11. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0283] The following shows the thickness of each layer of the structure constituting Example 1.

[0284] ε r1 The value is 2.56, S1 is 400 μm, and ε r2 The value is 2.56, S2 is 400 μm, and ε r The value is 2.56, S is 400 μm, w is 100 μm, t is 0.3 μm, and λ is 3123 μm. Furthermore, when n is 0, equation (1) is satisfied:

[0285] The total thickness of the layers constituting the structure of Example 1 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 1 has a thin-layer structure.

[0286] (Structure Creation)

[0287] The structure was designed and fabricated based on Example 1. The relative permittivity of a 400 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0288] Two 50mm square sheets were cut from the resin sheet. A 300nm thick copper layer was fabricated on both sides of the first sheet and on one side of the second sheet using copper sputtering. Dry film resist was applied to each copper layer, and the surface was exposed outside the metal pattern using an exposure machine (Nuvogo fine10, manufactured by Orbotech Co., Ltd.). The first sheet was shaped as a slit on the surface and a... Figure 2The first sheet is exposed in the pattern shown, and the second sheet is exposed in a slit-like manner with the copper layer present. After development, it is immersed in an aqueous copper chloride solution to etch the copper in the areas without dry film resist. The dry film resist remaining on the pattern is removed using an aqueous sodium hydroxide solution. The back side of the first sheet is then overlapped with the side of the second sheet without the metal pattern layer, thereby creating the structure of Example 1.

[0289] (Electromagnetic wave control efficiency)

[0290] The electromagnetic wave control efficiency of the structure fabricated in Example 1 was measured by the following method.

[0291] For the structure of Example 1, using an HFSS manufactured by ANSYS, the transmitted and incident electromagnetic waves of a 96 GHz electromagnetic wave were measured when the wave was incident perpendicularly from the top of the structure onto the third metal pattern layer 15, and the transmittance of the electromagnetic wave was calculated. The transmittance of the electromagnetic wave is expressed as (transmitted wave energy / incident wave energy) × 100. The polarization direction of the electric field of the electromagnetic wave is perpendicular to the slit direction of the third metal pattern layer 15.

[0292] As a result, the electromagnetic wave transmittance is 93.4%. The structure of Example 1 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0293] Therefore, the structure in Embodiment 1 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0294] [Example 2]

[0295] (Design of electromagnetic wave control components)

[0296] Figure 3 and 15 This is a diagram illustrating the second metal pattern layer in the structure fabricated in Example 2.

[0297] Reference Figure 1 , Figure 3 and Figure 15 A first dielectric layer 12 (1510 μm thick, relative permittivity 2.56) is disposed on a slit-shaped first metal pattern layer 11 (copper, 300 nm thick, 100 μm wide, and slit spacing 100 μm). A second metal pattern layer 13 (300 nm thick, such as...) is disposed on top of this layer with a spacing 'a' of 250 μm between the metal patterns. Figure 15As shown, a U-shaped copper structure with a width b of 100 μm, a longitudinal length of 750 μm, and a lateral length L is regularly arranged in repeating units with a longitudinal period of 1 mm and a transverse period of 1 mm. A second dielectric layer 14 (thickness 1510 μm and relative permittivity 2.56) is placed on top of this, and a slit-shaped third metal pattern layer 15 (copper, thickness 300 nm, width 100 μm, and slit spacing 100 μm) is placed on top of this, orthogonal to the first metal pattern layer. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0298] exist Figure 4 The text shows changes. Figure 3 The phase of the transmitted wave is calculated simultaneously using the shape number (shapes 1-4) and length L of the structures. Here, Figure 4 The number before the hyphen represents the value of the horizontal axis. Figure 3 The shape number in the diagram, with the number after the hyphen representing L (μm). Figure 4 The vertical axis represents the phase of the transmitted wave.

[0299] The second metal pattern layer is designed to function as a lens.

[0300] If the difference between the phase of the transmitted wave corresponding to the meta-atom at the center of the second metal pattern layer and the phase of the transmitted wave corresponding to the meta-atom at a distance r [mm] from the center of the second metal pattern layer is denoted as Δ [°], if the wavelength of the incident electromagnetic wave is set to λ[mm] and the focal length is set to f[mm], then the following equation (2) is satisfied.

[0301] [Number 1]

[0302] Here, λ is set to 3.123 mm, f is set to 30 mm, and the shape of the central superatom is set to be equivalent to... Figure 4 The shape of 1-530 (L is 530μm) Figure 3 Shape 1) described in the figure is used to determine the shape of the superatoms outside the center in a manner that satisfies Equation (2), and a second metal pattern layer with a square pattern having a side length of approximately 50 mm is designed. The results are shown in Figure 5 .

[0303] The following shows the thickness of each layer of the structure constituting Example 2.

[0304] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε rWhen the value is 2.56, S is 1510μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0305] The total thickness of the layers constituting the structure of Example 2 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 2 has a thin-layer structure.

[0306] (Structure Creation)

[0307] The structure was designed and fabricated based on Example 2. The relative permittivity of a 1510 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0308] Two 60mm square sheets are cut from the resin sheet. A copper layer with a thickness of 300nm is formed on both sides of the first sheet and on one side of the second sheet by copper sputtering.

[0309] Dry film resist was applied to each copper layer, and then exposed outside the metal pattern using an exposure machine (product name Nuvogo fine10, manufactured by Orbotech Co., Ltd.).

[0310] The first piece is shaped like a slit on the surface and a... Figure 5 The first sheet is exposed in the pattern shown, and the second sheet is exposed in a slit-like manner with the copper layer present. After development, it is immersed in an aqueous copper chloride solution to etch the copper in the areas without dry film resist. The dry film resist remaining on the pattern is removed using an aqueous sodium hydroxide solution. The back side of the first sheet is then aligned with the side of the second sheet without the metal pattern layer, thereby creating the structure of Example 2.

[0311] (Seamless fit)

[0312] In the structure of Example 2, the adhesion between the copper layer and the resin sheet was evaluated. The result showed that the copper peeling was classified as state 0, indicating high adhesion.

[0313] (Electromagnetic wave control efficiency)

[0314] The electromagnetic wave control efficiency of the structure fabricated in Example 2 was measured by the following method.

[0315] Reference Figure 6 The measurement of the electromagnetic wave intensity of the oscillator is explained.

[0316] A horn antenna 21 (MI-wave 261W-20 / 387) was mounted on an oscillator 20 (Terasense IMPATT-100 / 200-H / F 180mW). First, a millimeter-wave camera 22 (Terasense Tera-256) was placed 30mm from the front end of the horn antenna 21. The intensity of the electromagnetic waves emitted by the oscillator was measured by scanning the millimeter-wave camera 22 with an automatic stage (Sigma Optical Machinery OSMS26-200) and a controller (Sigma Optical Machinery HSC-103). The measured electromagnetic wave intensity was integrated over the measured area to calculate the total integrated intensity I. ref .

[0317] Next, refer to Figure 7 The measurement of electromagnetic wave intensity of the structure fabricated in Example 2 will be explained.

[0318] The structure 10 fabricated in Example 2 is placed 30 mm from the front end of the horn antenna 21, and a millimeter-wave camera 22 is placed 15 mm from the structure 10. The electromagnetic wave intensity is measured using the millimeter-wave camera 22 in the same manner as described above. The measured electromagnetic wave intensity is integrated with the measured area to calculate the transmission integral intensity I. sample Calculate (I) sample / I ref The transmittance was calculated as 100, and the result was 79.5%.

[0319] The structure of Example 2 is designed to satisfy the above formula (1), so it has high transmittance and high electromagnetic wave control efficiency.

[0320] Therefore, the structure in Embodiment 2 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0321] (Collimation of electromagnetic waves)

[0322] The collimation capability of the electromagnetic waves of the structure fabricated in Example 2 was determined using the following method.

[0323] Reference Figure 8 The left figure illustrates the measurement of the electromagnetic wave collimation capability of the structure fabricated in Example 2. It should be noted that... Figure 8 The right figure shows the structure, etc., with the vertical direction of the paper as the x-axis and the vertical direction of the structure, etc. as the y-axis.

[0324] The structure 10 fabricated in Example 2 is placed at a distance d1 from the front end of the horn antenna 21, and the millimeter-wave camera 22 is placed at a distance d2 from the structure 10. d1 is the distance between the front end of the horn antenna 21 and the structure 10, set to 10 mm. d2 is the distance between the structure 10 and the millimeter-wave camera 22, set to 50 mm, 100 mm, or 150 mm respectively. The intensity of the electromagnetic wave emitted by the oscillator 20 is measured using the millimeter-wave camera 22, and the half-width of the intensity distribution is taken as the beamwidth. The same measurement is performed with the same configuration but without the structure. The results are shown below. Figure 9 .

[0325] Here, Figure 9 The left figure shows the relationship between the beamwidth in the x-axis direction and the distance between the structure (lens) and the millimeter-wave camera. Figure 9 The right figure shows the relationship between the beamwidth in the y-axis direction and the distance between the structure (lens) and the millimeter-wave camera. Figure 9 The horizontal axis in the left and right images represents the distance (mm) between the structure (lens) and the millimeter-wave camera. Figure 9 The vertical axis of the left and right figures represents the beamwidth (mm).

[0326] It should be noted that, Figure 9 The solid lines in the left and right figures represent the results when no structure is placed (no structure). Figure 9 The dashed lines in the left and right figures represent the results when placing structures (with structures).

[0327] Without any structure in place, the beamwidth widens as the camera moves away.

[0328] On the other hand, when the structure fabricated in Embodiment 2 is placed, the rate of change of beamwidth in the x-axis direction is 118% when d2 changes from 50mm to 150mm, and the rate of change of beamwidth in the y-axis direction is 90% when d2 changes from 50mm to 150mm. The change in beamwidth is small, and it is confirmed that it is collimated.

[0329] (Focusing of electromagnetic waves)

[0330] The light-gathering ability of the electromagnetic waves of the structure fabricated in Example 2 was determined by the following method.

[0331] Reference Figure 10 The left figure illustrates the measurement of electromagnetic wave intensity of the structure fabricated in Example 2. It should be noted that... Figure 10 The right figure shows the structure, etc., with the vertical direction of the paper as the x-axis and the vertical direction of the structure, etc. as the y-axis.

[0332] The structure 10 fabricated in Example 2 is placed at a distance d3 from the front end of the horn antenna 21, and the millimeter-wave camera 22 is placed at a distance d4 from the structure 10.

[0333] d3 is the distance between the front end of the horn antenna 21 and the structure 10, set to 250mm. d4 is the distance between the structure 10 and the millimeter-wave camera 22, set to 30mm.

[0334] The intensity of the electromagnetic waves emitted by the oscillator is measured using a millimeter-wave camera 22, and the intensity distribution is as follows: Figure 11 As shown, the half-width of the intensity distribution is 2.9 mm, confirming that the electromagnetic wave is focused.

[0335] [Example 3]

[0336] (Design of electromagnetic wave control components)

[0337] Reference Figure 1 and Figure 2 A first dielectric layer 12 (1500 μm thick, relative permittivity 2.80) is disposed on a slit-shaped first metal patterned layer 11 (copper, 300 nm thick, 100 μm wide, and 100 μm slit spacing). A second metal patterned layer 13 (300 nm thick, such as...) is disposed on top of this layer. Figure 2 As shown, a U-shaped copper structure with a longitudinal length of 750 μm and a lateral length L of 400 μm is regularly arranged in repeating units with a longitudinal period of 1 mm and a lateral period of 1 mm. A second dielectric layer 14 (thickness 1500 μm and relative permittivity 2.80) is placed on top of this pattern. A slit-shaped third metal pattern layer 15 (copper, thickness 300 nm, width 100 μm, and slit spacing 100 μm) is then placed on top of this pattern, orthogonal to the first metal pattern layer. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0338] The following shows the thickness of each layer of the structure constituting Example 3.

[0339] ε r1 The value is 2.80, S1 is 1500 μm, and ε r2 The value is 2.80, S2 is 1500 μm, and ε r When the value is 2.80, S is 1500μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0340] The total thickness of the layers constituting the structure of Example 3 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 3 has a thin-layer structure.

[0341] (Structure Creation)

[0342] The structure was fabricated based on the above design. The relative permittivity of a 1500 μm thick polycarbonate resin sheet (product name EXL9330, manufactured by SABIC) was measured and found to be 2.80.

[0343] Two 60mm square wafers were cut from the resin sheet. A 300nm thick copper layer was fabricated on both sides of the first wafer and on one side of the second wafer using copper sputtering. The adhesion between the copper layer and the resin sheet was evaluated, and the copper peeling was classified as State 2. Dry film resist was applied to each copper layer, and exposure was performed outside the metal pattern using an exposure machine (Nuvogo fine10, manufactured by Orbotech Co., Ltd.). The first wafer was cut with a slit-like surface on the front and a... Figure 2 The first sheet is exposed in the pattern shown, and the second sheet is exposed in a slit-like manner with the copper layer present. After development, it is immersed in an aqueous copper chloride solution to etch the copper in the areas without dry film resist. The dry film resist remaining on the pattern is removed using an aqueous sodium hydroxide solution. The back side of the first sheet is then overlapped with the side of the second sheet without the metal pattern layer, thereby creating the structure of Example 3.

[0344] (Electromagnetic wave control efficiency)

[0345] For the structure in Example 3, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when a 96 GHz electromagnetic wave was incident perpendicularly from the top of the structure onto the third metal pattern layer. The polarization direction of the electromagnetic wave's electric field was perpendicular to the slit direction of the third metal pattern layer.

[0346] As a result, the electromagnetic wave transmittance is 88.2%. The structure of Example 3 is designed to satisfy the above formula (1), so it has high transmittance and high electromagnetic wave control efficiency.

[0347] Therefore, the structure in Embodiment 3 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0348] [Example 4]

[0349] (Design of electromagnetic wave control components)

[0350] Reference Figure 1 and Figure 2A first dielectric layer 12 (1500 μm thick, relative permittivity 2.20) is disposed on a slit-shaped first metal pattern layer 11 (copper, 300 nm thick, 100 μm wide, and slit spacing 100 μm). A second metal pattern layer 13 (300 nm thick, as shown in Figure 2, consisting of U-shaped copper structures with a longitudinal length of 750 μm and a lateral length L of 400 μm arranged regularly in repeating units with a longitudinal period of 1 mm and a lateral period of 1 mm) is disposed on this layer. A second dielectric layer 14 (1500 μm thick, relative permittivity 2.20) is disposed on this layer. A slit-shaped third metal pattern layer 15 (copper, 300 nm thick, 100 μm wide, and slit spacing 100 μm) is disposed on this layer, with the slit direction orthogonal to the first metal pattern layer. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0351] The following shows the thickness of each layer of the structure constituting Example 4.

[0352] ε r1 The value is 2.20, S1 is 1500 μm, and ε r2 The value is 2.20, S2 is 1500 μm, and ε r When the value is 2.20, S is 1500μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0353] The total thickness of the layers constituting the structure of Example 4 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 4 has a thin-layer structure.

[0354] (Structure Creation)

[0355] The structure was fabricated based on the above design. The relative permittivity of a 1500 μm thick polypropylene resin sheet (product name NOVATEC PPMG03BD, manufactured by Japan Polypropylene Co., Ltd.) was measured and found to be 2.20.

[0356] Two 60mm square sheets are cut from the resin sheet. A copper layer with a thickness of 300nm is formed on both sides of the first sheet and on one side of the second sheet by copper sputtering.

[0357] Dry film resist was applied to each copper layer, and then exposed outside the metal pattern using an exposure machine (product name Nuvogo fine10, manufactured by Orbotech Co., Ltd.). The first film was prepared with the surface forming a slit shape and the back forming... Figure 2The first sheet is exposed in the pattern shown, and the second sheet is exposed in a slit-like manner with the copper layer present. After development, it is immersed in an aqueous copper chloride solution to etch the copper in the areas without dry film resist. The dry film resist remaining on the pattern is removed using an aqueous sodium hydroxide solution. The back side of the first sheet is then aligned with the side of the second sheet without the metal pattern layer, thereby creating the structure of Example 4.

[0358] (Seamless fit)

[0359] In the structure of Example 4, the adhesion between the copper layer and the resin sheet was evaluated, and the copper peeling was classified as State 2.

[0360] (Electromagnetic wave control efficiency)

[0361] For the structure in Example 4, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when a 96 GHz electromagnetic wave was incident perpendicularly from the top of the structure onto the third metal pattern layer. The polarization direction of the electromagnetic wave's electric field was perpendicular to the slit direction of the third metal pattern layer.

[0362] As a result, the electromagnetic wave transmittance is 90.0%. The structure of Example 4 is designed to satisfy the above formula (1), so it has high transmittance and high electromagnetic wave control efficiency.

[0363] Therefore, the structure in Embodiment 4 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0364] [Example 5]

[0365] (Design of electromagnetic wave control components)

[0366] Reference Figure 1 , Figure 2 and Figure 3 A first dielectric layer 12 (1500 μm thick, relative permittivity 2.56) is disposed on a slit-shaped first metal patterned layer 11 (copper, 300 nm thick, 100 μm wide, and 100 μm slit spacing). A second metal patterned layer 13 (300 nm thick, for various applications) is then disposed on top of this first dielectric layer. Figure 3 Shape 2 described herein features a metal pattern of L-shaped copper structures with a transverse length L of 700 μm, arranged regularly in repeating units with a longitudinal period of 1 mm and a transverse period of 1 mm. A second dielectric layer 14 (thickness 1510 μm and relative permittivity 2.56) is placed on top of this pattern. A slit-shaped third metal pattern layer 15 (copper, thickness 300 nm, width 100 μm, and slit spacing 100 μm) is then placed on top of this pattern, orthogonal to the first metal pattern layer. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0367] The following shows the thickness of each layer of the structure constituting Example 5.

[0368] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε r When the value is 2.56, S is 1510μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0369] The total thickness of the layers constituting the structure of Example 5 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 5 has a thin-layer structure.

[0370] (Structure Creation)

[0371] The structure was fabricated following the same steps as in Example 2.

[0372] (Electromagnetic wave control efficiency)

[0373] For the structure in Example 5, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when an electromagnetic wave with a frequency of 96 GHz was incident perpendicularly from the top of the structure onto the third metal pattern layer. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal pattern layer.

[0374] As a result, the electromagnetic wave transmittance is 81.7%. The structure of Example 5 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0375] Therefore, the structure in Embodiment 5 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0376] [Example 6]

[0377] (Design of electromagnetic wave control components)

[0378] In the second metal patterned layer 13 of Example 5, a cuprous oxide layer (thickness 50 nm, relative permittivity 12) as a metal compound layer is disposed on the boundary side with the first dielectric layer 12 (in one embodiment, a metal compound layer is present inside the metaatoms), otherwise the structure is designed in the same way as in Example 5.

[0379] The following shows the thickness of each layer of the structure constituting Example 6.

[0380] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε rWhen the value is 2.56, S is 1510μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0381] The total thickness of the layers constituting the structure of Example 6 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 6 has a thin-layer structure.

[0382] (Preparation of compositions containing metal compounds)

[0383] 202 g of copper(II) acetate monohydrate (manufactured by Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 1890 g of distilled water (manufactured by Kyoei Pharmaceutical Co., Ltd.) and 874 g of 1,2-propanediol (manufactured by Kanto Chemical Co., Ltd.), and the solution temperature was maintained at -5°C using an external thermostat. 59 g of hydrazine monohydrate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the resulting solution over 20 minutes. After stirring for 30 minutes under a nitrogen atmosphere, the solution temperature was maintained at 25°C using an external thermostat, and stirring was continued for 90 minutes. Following stirring, the dispersion was separated into a supernatant and a precipitate by centrifugation. A mixture of 17g of DISPERBYK-145 (manufactured by BYK Chemical Co., Ltd.) and 100g of ethanol (manufactured by Fujifilm and Koichi Pure Chemical Co., Ltd.) as a non-volatile organic compound was added to 98g of the obtained precipitate, and the mixture was dispersed using a homogenizer to obtain 216g of a composition containing a metal-containing compound with 30% by mass cuprous oxide particles.

[0384] (Structure Creation)

[0385] The structure was designed and fabricated based on Example 6. The relative permittivity of a 1510 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0386] Two 60mm square sheets were cut from the resin sheet, and copper layers with a thickness of 300nm were fabricated on one side of each sheet by copper sputtering.

[0387] Dry film resist is applied to each copper layer, and the area outside the metal pattern is exposed using an exposure machine (product name Nuvogo fine10, manufactured by Orbotech Co., Ltd.). After development, the copper areas without dry film resist are etched by immersing them in an aqueous copper chloride solution. The remaining dry film resist on the pattern is then removed using an aqueous sodium hydroxide solution.

[0388] On the back of the first piece where no copper layer exists, a composition containing a metal compound is spin-coated at 1400 rpm using a spin coater and then dried at 60°C for 60 minutes, thereby forming a coated film.

[0389] Multiple metaatoms were formed by irradiating the coated film with a laser (laser intensity: 15mW) in the manner of the design pattern of Example 6. Excess metal-containing compound coating on the non-irradiated areas was removed by rinsing with purified water, aligning the back side of the first sheet with the side of the second sheet without the metal pattern layer, thereby fabricating the structure of Example 6. The total thickness of the metaatoms was 300 nm. Inside the metaatoms, a cuprous oxide layer as the metal compound layer was formed with a thickness of 50 nm.

[0390] (Electromagnetic wave control efficiency)

[0391] For the structure in Example 6, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when a 96 GHz electromagnetic wave was incident perpendicularly from the top of the structure onto the third metal pattern layer. The polarization direction of the electromagnetic wave's electric field was perpendicular to the slit direction of the third metal pattern layer.

[0392] As a result, the electromagnetic wave transmittance is 82.9%. The structure of Example 6 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0393] Therefore, the structure in Embodiment 6 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0394] [Example 7]

[0395] (Design of electromagnetic wave control components)

[0396] In the second metal patterned layer 13 fabricated in Example 5, a cuprous oxide layer (thickness 80 nm, relative permittivity 12) as a metal compound layer is disposed on the boundary side with the first dielectric layer 12 (in one embodiment, a metal compound layer is present inside the metaatoms), otherwise the structure is designed in the same manner as in Example 5.

[0397] The following shows the thickness of each layer of the structure constituting Example 7.

[0398] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε r When the value is 2.56, S is 1510μm, w is 100μm, t is 0.3μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0399] The total thickness of the layers constituting the structure of Example 7 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 7 has a thin-layer structure.

[0400] (Preparation of compositions containing metal compounds)

[0401] The composition containing the metal compound was prepared by the same procedure as in Example 6.

[0402] (Structure Creation)

[0403] The drying time after spin-coating the metal compound-containing composition onto the back side of the first sheet, where no copper layer exists, was reduced to 5 minutes. Otherwise, the structure was fabricated following the same steps as in Example 6. The total thickness of the metaatoms was 300 nm. A copper oxide layer, serving as the metal compound layer, was formed within the metaatoms with a thickness of 80 nm.

[0404] (Electromagnetic wave control efficiency)

[0405] For the structure of Example 7, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when an electromagnetic wave with a frequency of 96 GHz was incident perpendicularly from the top of the structure onto the dielectric layer. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal pattern layer.

[0406] As a result, the electromagnetic wave transmittance is 82.5%. The structure of Example 7 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0407] Therefore, the structure in Embodiment 7 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0408] [Example 8]

[0409] (Design of electromagnetic wave control components)

[0410] The thickness of the second metal pattern layer 13 is 1 μm, and a cuprous oxide layer (thickness 200 nm, relative permittivity 12) is disposed as a metal compound layer on the boundary side with the first dielectric layer 12 (in one embodiment, a metal compound layer is present inside the metaatoms). Otherwise, the structure is designed in the same manner as in Example 5.

[0411] The following shows the thickness of each layer of the structure constituting Example 8.

[0412] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε r When the value is 2.56, S is 1510μm, w is 100μm, t is 1μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0413] The total thickness of the layers constituting the structure of Example 8 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 8 has a thin-layer structure.

[0414] (Preparation of compositions containing metal compounds)

[0415] The composition containing the metal compound was prepared by the same procedure as in Example 6.

[0416] (Structure Creation)

[0417] The spin-coating speed for the metal compound-containing composition on the back of the first sheet, where no copper layer exists, was set to 500 rpm. Otherwise, the structure was fabricated following the same steps as in Example 6. The total thickness of the metaatoms was 1 μm. A cuprous oxide layer, serving as the metal compound layer, was formed within the metaatoms with a thickness of 200 nm.

[0418] (Electromagnetic wave control efficiency)

[0419] For the structure in Example 8, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when an electromagnetic wave with a frequency of 96 GHz was incident perpendicularly from the top of the structure onto the third metal pattern layer. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal pattern layer.

[0420] As a result, the electromagnetic wave transmittance is 83.5%. The structure of Example 8 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0421] Therefore, the structure in Embodiment 8 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0422] [Example 9]

[0423] (Design of electromagnetic wave control components)

[0424] The thickness of the second metal pattern layer 13 is 4.1 μm, and a cuprous oxide layer (thickness 1.1 μm, relative permittivity 12) as a metal compound layer is disposed on the boundary side with the first dielectric layer 12 (in one embodiment, a metal compound layer is present inside the metaatoms). Otherwise, the structure is designed in the same manner as in Example 5.

[0425] The following shows the thickness of each layer of the structure constituting Example 9.

[0426] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε r When the value is 2.56, S is 1510μm, w is 100μm, t is 4.1μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0427] The total thickness of the layers constituting the structure of Example 9 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 9 has a thin-layer structure.

[0428] (Preparation of compositions containing metal compounds)

[0429] The composition containing the metal compound was prepared by the same procedure as in Example 6.

[0430] (Structure Creation)

[0431] The drying time after spin-coating the metal compound-containing composition onto the back side of the first sheet where no copper layer was present was set to 5 minutes, and the laser irradiation intensity on the coated film was set to 28 mW. Otherwise, the structure was fabricated following the same steps as in Example 6. The total thickness of the metaatoms was 4.1 μm. A cuprous oxide layer, serving as the metal compound layer, was formed within the metaatoms with a thickness of 1.1 μm.

[0432] (Electromagnetic wave control efficiency)

[0433] For the structure of Example 9, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when an electromagnetic wave with a frequency of 96 GHz was incident perpendicularly from the top of the structure onto the dielectric layer. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal pattern layer.

[0434] As a result, the electromagnetic wave transmittance is 84.7%. The structure of Example 9 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0435] Therefore, the structure of Embodiment 9 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0436] [Example 10]

[0437] (Design of electromagnetic wave control components)

[0438] The thickness of the second metal pattern layer 13 is 4.1 μm, and a metal compound layer (relative permittivity 12) with a thickness of 1.1 μm is configured to be sandwiched from both sides by a copper layer with a thickness of 1.5 μm (in one embodiment, a metal compound layer is present inside the metaatoms). Otherwise, the structure is designed in the same manner as in Example 5.

[0439] The following shows the thickness of each layer of the structure constituting Example 10.

[0440] ε r1 The value is 2.56, S1 is 1510 μm, and ε r2 The value is 2.56, S2 is 1510 μm, and ε rWhen the value is 2.56, S is 1510μm, w is 100μm, t is 4.1μm, λ is 3123μm, and n is 1, the above equation (1) is satisfied.

[0441] The total thickness of the layers constituting the structure of Example 10 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 10 has a thin-layer structure.

[0442] (Preparation of compositions containing metal compounds)

[0443] The composition containing the metal compound was prepared by the same procedure as in Example 6.

[0444] (Structure Creation)

[0445] The drying time after spin-coating the metal compound-containing composition onto the back side of the first sheet without a copper layer was set to 5 minutes, and the laser irradiation intensity on the coated film was set to 28 mW. A nitrogen atmosphere was used during laser irradiation. Otherwise, the structure was fabricated following the same steps as in Example 6. The total thickness of the meta-atoms was 4.1 μm. A cuprous oxide layer with a thickness of 1.1 μm was formed inside the meta-atoms as a metal compound layer, and copper layers with a thickness of 1.5 μm were formed on both sides of the meta-atoms in the thickness direction.

[0446] (Electromagnetic wave control efficiency)

[0447] For the structure of Example 10, the transmittance was calculated using HFSS (Answer Keyboard Surveillance System) manufactured by ANSYS when an electromagnetic wave with a frequency of 96 GHz was incident perpendicularly from the top of the structure onto the third metal patterned layer. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal patterned layer.

[0448] As a result, the electromagnetic wave transmittance is 85.0%. The structure of Example 10 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0449] Therefore, the structure of Embodiment 10 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0450] [Example 11]

[0451] (Design of electromagnetic wave control components)

[0452] Reference Figure 1 and Figure 12 The following structure was designed: a first dielectric layer 12 (thickness 135μm and relative permittivity 2.56) was disposed on a slit-shaped first metal patterned layer 11 (copper, thickness 300nm, width 35μm and slit spacing 35μm), and a second metal patterned layer 13 (thickness 300nm, such as...) was disposed on top of it. Figure 12As shown, a U-shaped copper structure (with a longitudinal length of 250 μm and a lateral length of L135 μm) is regularly arranged with repeating units of 334 μm in the longitudinal direction and 334 μm in the transverse direction. A second dielectric layer 14 (135 μm thick and with a relative permittivity of 2.56) is disposed on the pattern. A slit-shaped third metal pattern layer 15 (copper, 300 nm thick, 35 μm wide, and with a slit spacing of 35 μm) is disposed on the pattern layer 15, orthogonal to the first metal pattern layer 11. The wavelength λ of the incident electromagnetic wave is 999.3 μm.

[0453] The following shows the thickness of each layer of the structure constituting Example 11.

[0454] ε r1 The value is 2.56, S1 is 135 μm, and ε r2 The value is 2.56, S2 is 135 μm, and ε r The value is 2.56, S is 135μm, w is 35μm, t is 0.3μm, and λ is 999.3μm. Furthermore, when n is 0, equation (1) above is satisfied.

[0455] The total thickness of the layers constituting the structure of Example 11 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 11 has a thin-layer structure.

[0456] (Structure Creation)

[0457] The structure was fabricated based on the above design. The relative permittivity of a 135 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0458] The structure of Example 11 was made by following the same steps as in Example 1.

[0459] (Electromagnetic wave control efficiency)

[0460] The electromagnetic wave control efficiency of the structure fabricated in Example 11 was measured by the following method.

[0461] For the structure of Example 11, using an HFSS manufactured by ANSYS, the transmitted and incident electromagnetic waves were measured when an electromagnetic wave with a frequency of 300 GHz was incident perpendicularly from the top of the structure onto the third metal patterned layer, and the transmittance of the electromagnetic wave was calculated. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal patterned layer.

[0462] As a result, the electromagnetic wave transmittance is 94.9%. The structure of Example 11 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0463] Therefore, the structure of Embodiment 11 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0464] [Example 12]

[0465] (Design of electromagnetic wave control components)

[0466] Reference Figure 1 and Figure 13 The following structure was designed: a first dielectric layer 12 (40 μm thick and with a relative permittivity of 2.56) was disposed on a slit-shaped first metal patterned layer 11 (copper, 300 nm thick, 10 μm wide, and 10 μm slit spacing), and a second metal patterned layer 13 (300 nm thick, as shown in the figure) was disposed on top of it. Figure 13 As shown, a U-shaped copper structure (with a longitudinal length of 75 μm and a lateral length of L40 μm) is regularly arranged in repeating units with a longitudinal period of 100 μm and a lateral period of 100 μm. A second dielectric layer 14 (with a thickness of 40 μm and a relative permittivity of 2.56) is disposed on the pattern. A slit-shaped third metal pattern layer 15 (copper, with a thickness of 300 nm, a width of 10 μm, and a slit spacing of 10 μm) is disposed on the pattern layer 15, orthogonal to the first metal pattern layer 11. The wavelength λ of the incident electromagnetic wave is 285.5 μm.

[0467] The following shows the thickness of each layer of the structure constituting Example 12.

[0468] ε r1 The value is 2.56, S1 is 40 μm, and ε r2 The value is 2.56, S2 is 40 μm, and ε r The value is 2.56, S is 40 μm, w is 10 μm, t is 0.3 μm, and λ is 285.5 μm. Furthermore, when n is 0, equation (1) above is satisfied.

[0469] The total thickness of the layers constituting the structure of Example 12 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 12 has a thin-layer structure.

[0470] (Structure Creation)

[0471] The structure was fabricated based on the design of Example 12. The relative permittivity of a 135 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0472] The structure of Example 12 was made by following the same steps as in Example 1.

[0473] (Electromagnetic wave control efficiency)

[0474] The electromagnetic wave control efficiency of the structure fabricated in Example 12 was measured by the following method.

[0475] For the structure of Example 12, using an HFSS manufactured by ANSYS, the transmitted and incident electromagnetic waves were measured when an electromagnetic wave with a frequency of 1.05 THz was incident perpendicularly from the top of the structure onto the third metal pattern layer, and the transmittance of the electromagnetic wave was calculated. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal pattern layer.

[0476] As a result, the electromagnetic wave transmittance is 95.3%. The structure of Example 12 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0477] Therefore, the structure of Embodiment 12 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0478] [Example 13]

[0479] (Design of electromagnetic wave control components)

[0480] Reference Figure 1 and Figure 14 The following structure was designed: a first dielectric layer 12 (thickness 600 μm and relative permittivity 2.56) is disposed on a slit-shaped first metal patterned layer 11 (copper, thickness 300 nm, width 150 μm and slit spacing 150 μm), and a second metal patterned layer 13 (thickness 300 nm, such as...) is disposed on top of it. Figure 14 As shown, a U-shaped copper structure (with a longitudinal length of 1125 μm and a lateral length of L600 μm) is regularly arranged with repeating units of 1500 μm in the longitudinal direction and 1500 μm in the transverse direction. A second dielectric layer 14 (thickness 600 μm and relative permittivity 2.56) is disposed on the pattern. A slit-shaped third metal pattern layer 15 (copper, thickness 300 nm, width 150 μm, and slit spacing 150 μm) is disposed on the pattern layer 15 with slits orthogonal to the first metal pattern layer 11. The wavelength λ of the incident electromagnetic wave is 4997 μm.

[0481] The following shows the thickness of each layer of the structure constituting Example 13.

[0482] ε r1 The value is 2.56, S1 is 600 μm, and ε r2 The value is 2.56, S2 is 600 μm, and ε r The value is 2.56, S is 600 μm, w is 150 μm, t is 0.3 μm, and λ is 4997 μm. Furthermore, when n is 0, equation (1) above is satisfied.

[0483] The total thickness of the layers constituting the structure of Example 13 is less than 10 times the wavelength of the incident electromagnetic wave λ, therefore the structure of Example 13 has a thin-layer structure.

[0484] (Structure Creation)

[0485] The structure was fabricated based on the design of Example 13. The relative permittivity of a 600 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0486] The structure of Example 13 was made by following the same steps as in Example 1.

[0487] (Electromagnetic wave control efficiency)

[0488] The electromagnetic wave control efficiency of the structure fabricated in Example 13 was measured by the following method.

[0489] For the structure of Example 13, using an HFSS manufactured by ANSYS, the transmitted and incident electromagnetic waves were measured when a 60 GHz electromagnetic wave was incident perpendicularly from the top of the structure onto the third metal patterned layer, and the transmittance of the electromagnetic wave was calculated. The polarization direction of the electric field of the electromagnetic wave was perpendicular to the slit direction of the third metal patterned layer.

[0490] As a result, the electromagnetic wave transmittance is 87.5%. The structure of Example 13 is designed to satisfy the above formula (1), thus it has high transmittance and high electromagnetic wave control efficiency.

[0491] Therefore, the structure of Embodiment 13 is a structure with a thin layer structure and high electromagnetic wave control efficiency.

[0492] [Comparative Example 1]

[0493] (Design of electromagnetic wave control components)

[0494] The first and third metal pattern layers are replaced with the second metal pattern layer in Example 1, except that the structure is the same as in Example 1. The wavelength λ of the incident electromagnetic wave is 3123 μm.

[0495] (Structure Creation)

[0496] The structure was designed and fabricated based on Comparative Example 1. The relative permittivity of a 400 μm thick modified polyphenylene ether resin sheet (product name XYRON, manufactured by Asahi Kasei Corporation) was measured and found to be 2.56.

[0497] Two 50mm square sheets were cut from the resin sheet. A 300nm thick copper layer was fabricated on both sides of the first sheet and on one side of the second sheet using copper sputtering. Dry film resist was applied to each copper layer, and the surface was exposed outside the metal pattern using an exposure machine (Nuvogo fine10, manufactured by Orbotech Co., Ltd.). The first sheet was fabricated on both sides... Figure 2 The second piece is exposed in the manner shown in the pattern, with the copper layer present on the surface. Figure 2 The pattern shown was exposed. After development, the copper in the areas without dry film resist was etched by immersion in an aqueous copper chloride solution. The dry film resist remaining on the pattern was removed using an aqueous sodium hydroxide solution. The back side of the first sheet was then overlapped with the side of the second sheet without the metal pattern layer, thereby creating the structure of Comparative Example 1.

[0498] (Electromagnetic wave control efficiency)

[0499] The electromagnetic wave control efficiency of the structure fabricated in Comparative Example 1 was measured by the following method.

[0500] For the structure of Comparative Example 1, using an HFSS manufactured by ANSYS, the transmitted and incident electromagnetic waves were measured when a 96 GHz electromagnetic wave was incident perpendicularly from the top of the structure onto the third metal patterned layer, and the transmittance of the electromagnetic wave was calculated. The transmittance of the electromagnetic wave is expressed as (transmitted wave energy / incident wave energy) × 100. The result showed that the transmittance of the electromagnetic wave was 24.4%. The structure of Comparative Example 1 has low transmittance because the first and third metal patterned layers are not slit structures.

[0501] Industrial applicability

[0502] The structure of the present invention has a thin-layer structure and high electromagnetic wave control efficiency, and is therefore particularly suitable for application in electromagnetic wave control components.

[0503] Explanation of reference numerals in the attached figures

[0504] 10 Structure

[0505] 11 First Metal Pattern Layer

[0506] 12 First dielectric layer

[0507] 13 Second Metal Pattern Layer

[0508] 14 Second dielectric layer

[0509] 15 Third Metal Pattern Layer

[0510] 16 Superatoms

[0511] 17 Metal compound layer

[0512] 18 Resin Layers

[0513] 20 Oscillators

[0514] 21 Horn Antenna

[0515] 22mm wave camera

[0516] 23 Electromagnetic wave oscillation antenna

[0517] 24 Information Terminals

[0518] 25 Electromagnetic wave transceiver system

[0519] W1 transmits radio waves

[0520] W2 receives radio waves

Claims

1. A structure comprising, sequentially having a first metal pattern layer, a first dielectric layer, a second metal pattern layer, a second dielectric layer, and a third metal pattern layer, wherein, The first metal pattern layer and the third metal pattern layer have a slit-like structure. The second metal patterned layer contains metaatoms.

2. The structure according to claim 1, wherein, The metaatom also contains a layer of metal compound.

3. The structure according to claim 1 or 2, wherein, The metaatoms contain copper.

4. The structure according to claim 2, wherein, The metal constituting the metaatoms and the metal compound layer contains copper.

5. The structure according to claim 1 or 2, wherein, A resin layer is also provided on the outside of the first metal pattern layer and the third metal pattern layer.

6. The structure according to claim 1 or 2, wherein, The relative permittivity of the first dielectric layer is set to ε. r1 Let the thickness of the first dielectric layer be S1, with units of μm, and let the relative permittivity of the second dielectric layer be ε. r2 When the thickness of the second dielectric layer is set to S2, with units of μm, ε r2 / ε r1 When S2 / S1 is above 0.9 and below 1.1, In ε r1 With ε r2 Let the average value be ε r When the average value of S1 and S2 is set as S, and its unit is μm, the width of the metaatom is set as w, and its unit is μm, the thickness of the metaatom is set as t, and its unit is μm, and the wavelength of the incident electromagnetic wave is set as λ, and its unit is μm, the following equation (1) is satisfied: In equation (1), n ​​is an integer greater than or equal to 0.

7. The structure according to claim 1 or 2, wherein, The second metal pattern layer has a three-dimensional curved surface shape.

8. The structure according to claim 1 or 2, wherein, The carbon / metal elemental concentration ratio of the metaatom is above 0.05 and below 6.

0.

9. The structure according to claim 1 or 2, wherein, The water absorption rate of the dielectric contained in the first dielectric layer and the water absorption rate of the dielectric contained in the second dielectric layer are both below 0.

2.

10. The structure according to claim 1 or 2, wherein the thickness is more than 20 μm and less than 150 mm.

11. The structure according to claim 1 or 2, wherein, When electromagnetic waves are irradiated, the incident wave and the transmitted wave have different polarization directions.

12. The structure according to claim 1 or 2, wherein, The area of ​​the second metal pattern layer is 0.09 mm. 2 Above 20m 2 the following.

13. The structure according to claim 1 or 2, wherein, The operating frequency is above 0.3GHz and below 10THz.

14. An electromagnetic wave transceiver system comprising the structure and electromagnetic wave oscillation antenna as described in claim 1 or 2.

Citation Information

Patent Citations

  • Lens antenna device

    JP2020017878A

  • Lens antenna

    JP2021197656A